Adhesive composition for optical film

CN122953288APending Publication Date: 2026-10-20NIPPON SHOKUBAI CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202580021290.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-10-15
Filing Date
2025-03-18
Publication Date
2026-10-20

AI Technical Summary

Benefits of technology

根据本发明,能提供一种即便为厚膜,也能形成折射率及透明性提高的粘合剂的粘合剂组合物。由该粘合剂组合物形成的粘合剂即便为厚膜,折射率及透明性也提高,因此适合用作光学膜用粘合剂。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The problem of the present invention is to provide an adhesive composition for optical films that can form an adhesive with improved refractive index and transparency even when the adhesive layer is formed into a thick film. The adhesive composition for optical films of the present invention is characterized by comprising a copolymer (A), a monomer (a), and inorganic particles (B). The copolymer (A) comprises a structural unit (A1) derived from an aromatic hydrocarbon-containing (meth)acrylate monomer (a1) and a structural unit (A2) derived from a hydroxyl-containing (meth)acrylate monomer (a2). The monomer (a) comprises an aromatic hydrocarbon-containing (meth)acrylate monomer (a1) and a hydroxyl-containing (meth)acrylate monomer (a2). The content of the structural unit (A2) in the copolymer (A) is 1 to 40% by mass, and the content of the monomer (a) is 7 to 30% by mass in 100% by mass of the copolymer (A) and monomer (a).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to an adhesive composition for optical films. Background Technology

[0002] Image display devices such as liquid crystal displays, organic EL (electroluminescence) displays, and plasma display panels, as well as optical discs, possess optical films such as polarizing plates, phase retardation plates, optical compensation films, brightness enhancement films, and light diffusion films. When bonding optical films to each other or to other components, methods using high-refractive-index adhesives are known to avoid impairing the functionality of the optical films.

[0003] For example, Patent Document 1 discloses an adhesive composition in which a (meth)acrylate polymer, which contains monomers having multiple aromatic rings and monomers having hydroxyl groups as monomer units constituting the polymer, is the main component.

[0004] Existing technical documents Patent documents Patent Document 1: Japanese Patent Application Publication No. 2017-128732 Summary of the Invention The problem that the invention aims to solve The adhesive formed from the adhesive composition of Patent Document 1 requires a further increase in refractive index. Regarding further increasing the refractive index, methods involving the inclusion of inorganic particles in the adhesive are known. However, inorganic particles have poor compatibility with (meth)acrylate polymers, and even when the resulting adhesive layer has excellent transparency at a thickness of approximately 20 µm, the inventors have found that when it is made into a thick film with a thickness of 50 µm or more, which is required for adhesives used in optical films, it does not exhibit sufficient transparency.

[0005] Therefore, the problem of the present invention is to provide an adhesive composition that can form an adhesive with improved refractive index and transparency even when the adhesive layer is formed into a thick film.

[0006] Solution for solving the problem In order to solve the aforementioned problem, the inventors conducted repeated and in-depth research and discovered that when an adhesive composition containing (meth)acrylate polymer and inorganic particles contains a predetermined amount of the same monomer as the monomer constituting the polymer in monomer form without polymerization, an adhesive with improved refractive index and transparency can be obtained even when the composition is made into a coating film with a thickness of 50 µm or more, thus completing the present invention.

[0007] That is, the present invention is as follows.

[0008] [1] An adhesive composition for optical films is a composition comprising a (meth)acrylate copolymer (A), a (meth)acrylate monomer (a), and inorganic particles (B). The copolymer (A) comprises structural units (A1) derived from aromatic hydrocarbon-containing (meth)acrylate monomers (a1) and structural units (A2) derived from hydroxyl-containing (meth)acrylate monomers (a2). The monomer (a) comprises an aromatic hydrocarbon group-containing (meth)acrylate monomer (a1) and a hydroxyl group-containing (meth)acrylate monomer (a2). The content of the structural unit (A2) is 1-40% by mass in 100% by mass of the copolymer (A). The content of the monomer (a) is 7 to 30% by mass in 100% by mass of the copolymer (A) and the monomer (a).

[0009] [2] According to the adhesive composition described in [1], wherein, The monomer (a1) is at least one selected from the group consisting of aryl esters of (meth)acrylic acid, aralkyl esters of (meth)acrylic acid, and aryloxyalkyl esters of (meth)acrylic acid. The aryl esters, aralkyl esters, and aryloxyalkyl esters of (meth)acrylic acid are optionally bonded with aryl, arylalkyl, aryloxy, or aryloxyalkyl groups. The aryl esters, aralkyl esters, and aryloxyalkyl esters of (meth)acrylic acid are optionally epoxide-modified.

[0010] [3] According to the adhesive composition described in [1] or [2], wherein, The copolymer (A) comprises structural units (A3) derived from monomers other than aromatic hydrocarbon (meth)acrylate monomers (a1) and hydroxyl-containing (meth)acrylate monomers (a2). The (meth)acrylate monomer (a) includes other monomers (a3) ​​besides the (meth)acrylate monomer (a1) containing an aromatic hydrocarbon group and the (meth)acrylate monomer (a2) containing a hydroxyl group. The content of the structural unit (A3) is less than 50% by mass in 100% by mass of the copolymer (A).

[0011] [4] According to the adhesive composition described in [3], wherein, The other monomers (a3) ​​comprise at least one from the group consisting of (meth)acrylate monomers containing alicyclic hydrocarbon groups, (meth)acrylate monomers containing nitrogen atoms, (meth)acrylate monomers containing alkoxyalkyl groups, low Tg (meth)acrylate alkyl monomers with a glass transition temperature of less than -20°C for homopolymers, and monomers containing acid groups.

[0012] [5] The adhesive composition according to any one of [1] to [4], wherein, The copolymer (A) has a weight-average molecular weight of 500,000 to 3,000,000.

[0013] [6] The adhesive composition according to any one of [1] to [5], wherein, The inorganic particle (B) is a particle composed of at least one selected from the group consisting of alumina, titanium oxide, zirconium oxide, indium oxide, zinc oxide, tin oxide, lanthanum oxide, yttrium oxide, cerium oxide, magnesium oxide, niobium oxide, tantalum oxide, indium tin oxide, antimony tin oxide, barium titanate, strontium titanate, perovskite and spinel.

[0014] [7] The adhesive composition according to any one of [1] to [6], wherein, The volume average particle size of the inorganic particles (B) is 1–100 nm.

[0015] [8] The adhesive composition according to any one of [1] to [7], wherein, In the particle size determination of the inorganic particles (B) using dynamic light scattering, the ratio of the cumulative 90% particle size D90 of the volume reference to the cumulative 50% particle size D50 of the volume reference (D90 / D50) is 3.0 or less.

[0016] [9] The adhesive composition according to any one of [1] to [8], wherein, The refractive index of the adhesive layer formed from the adhesive composition is 1.58 to 1.80.

[0017] [10] The adhesive composition according to any one of [1] to [9], wherein, The haze of an adhesive layer with a thickness of 100µm formed from the adhesive composition is less than 1.0%.

[0018] [11] An adhesive layer formed from an adhesive composition according to any one of [1] to

[10] .

[0019] [12] Use of a composition according to any one of [1] to

[10] for use as an adhesive laminated on an optical film.

[0020] [13] A laminate comprising an optical film and an adhesive layer according to

[11] laminated on the optical film.

[0021] [14] A method for manufacturing an optical film laminated with an adhesive, comprising: A coating process for applying the composition according to any one of [1] to

[10] onto a substrate; and The process of forming an adhesive layer by drying and / or photocuring the coating layer obtained in the coating process. The substrate used in the coating process is an optical film, or the process may further include a transfer process after the adhesive layer formation process to transfer the adhesive layer onto the optical film.

[0022] [15] An adhesive layer comprising an (meth)acrylate copolymer (A) and inorganic particles (B) for use in optical films. The thickness of the adhesive layer is 50µm or more. The haze of the adhesive layer is below 1.0%. The copolymer (A) comprises structural units (A1) derived from aromatic hydrocarbon-containing (meth)acrylate monomers (a1) and structural units (A2) derived from hydroxyl-containing (meth)acrylate monomers (a2). The content of the structural unit (A2) is 1 to 40% by mass in 100% by mass of the copolymer (A).

[0023] Invention Effects According to the present invention, an adhesive composition is provided that can form an adhesive with improved refractive index and transparency even in thick films. The adhesive formed from this adhesive composition exhibits improved refractive index and transparency even in thick films, and is therefore suitable for use as an adhesive for optical films. Detailed Implementation

[0024] 1. Adhesive composition The adhesive composition of the present invention is preferably used for optical films and comprises a (meth)acrylate copolymer (A) (hereinafter sometimes simply referred to as copolymer (A)), a (meth)acrylate monomer (a) (hereinafter sometimes simply referred to as monomer (a)), and inorganic particles (B). By including copolymer (A), adhesiveness is exhibited, and by including inorganic particles (B), the refractive index of the adhesive layer is increased, making it suitable for bonding (adhesive bonding) of optical films. Moreover, although transparency usually tends to decrease when inorganic particles (B) are included, the present adhesive composition, by including monomer (a), improves the dispersibility of inorganic particles (B) in the adhesive composition. Furthermore, even after reducing the proportion of monomer (a) to allow the adhesive composition to cure after coating, high dispersibility is maintained, thereby improving the transparency of the adhesive layer.

[0025] 1.1 (Meth)acrylate copolymers (A) The (meth)acrylate copolymer (A) comprises structural units (A1) derived from an aromatic hydrocarbon-containing (meth)acrylate monomer (a1) (hereinafter, sometimes simply referred to as aromatic monomer (a1) or monomer (a1)) and structural units (A2) derived from a hydroxyl-containing (meth)acrylate monomer (a2) (hereinafter, sometimes simply referred to as hydroxyl-containing monomer (a2) or monomer (a2)). By including the aromatic structural unit (A1), the refractive index of the adhesive layer can be increased, making it suitable for use in optical films. Furthermore, the refractive index difference with inorganic particles (B) can be reduced, contributing to improved transparency of the adhesive layer. By including the hydroxyl-containing structural unit (A2), the affinity with inorganic particles (B) can be increased. Furthermore, the formation of water droplets in the adhesive layer under humidified conditions can be reduced, also improving transparency under humidified conditions.

[0026] 1.1.1 Aromatic structural unit (A1) The aromatic monomer (a1) that becomes the aromatic structural unit (A1) is preferably a monomer having an aromatic hydrocarbon ring (sometimes called an aryl unit) and a (meth)acryloyl group within its molecule. Examples of aromatic monomers (a1) include aryl esters of (meth)acrylic acid, aralkyl esters of (meth)acrylic acid (i.e., arylalkyl esters of (meth)acrylic acid), and aryloxyalkyl esters of (meth)acrylic acid. These can be used alone or in combination of two or more.

[0027] It should be noted that the aryl esters, aralkyl esters, and aryloxyalkyl esters of (meth)acrylic acid can be bonded with aromatic substituents having an aromatic hydrocarbon ring, such as aryl, arylalkyl, aryloxy, or aryloxyalkyl groups.

[0028] Furthermore, the aryl esters, aralkyl esters, and aryloxyalkyl esters of (meth)acrylic acid can be epoxide-modified products.

[0029] The aryl units contained in the aryl esters of (meth)acrylate, arylalkyl esters of (meth)acrylate (i.e., arylalkyl esters), aryloxyalkyl esters of (meth)acrylate, aryl, arylalkyl, aryloxy and aryloxyalkyl, etc., include benzene ring units, naphthyl ring units, azurite ring units, anthracene ring units, phenanthrene ring units, pyrene ring units, chrysene ring units, tetraphenyl ring units, triphenylene ring units, fluorene ring units, dinaphthothiophene ring units, etc., preferably benzene ring units, naphthyl ring units, fluorene ring units, etc. Furthermore, by bonding aromatic substituents such as aryl, arylalkyl, aryloxy, and aryloxyalkyl groups to aryl methacrylates, arylalkyl methacrylates (i.e., arylalkyl esters), or aryloxyalkyl methacrylates, groups containing multiple aryl groups can be formed. Examples of such groups containing multiple aryl groups include biphenylcycloyl, phenoxybenzyl, ortho-terphenylcycloyl, meta-terphenylcycloyl, and para-terphenylcycloyl.

[0030] The alkyl units contained in the arylalkyl esters (i.e., arylalkyl esters), aryloxyalkyl esters (meth)acrylates, arylalkyl and aryloxyalkyl esters include alkyl units with 1 to 10 carbon atoms, preferably including 1 to 4 carbon atoms, and more preferably including alkyl units with 1 to 2 carbon atoms.

[0031] The epoxides include ethylene oxide, propylene oxide, etc., and are preferably ethylene oxide.

[0032] As aromatic monomers (a1), specifically, examples include benzyl (meth)acrylate, phenyl (meth)acrylate, benzyl phenyl (meth)acrylate, p-phenyl benzyl (meth)acrylate, o-phenylphenol (meth)acrylate, ethoxylated o-phenylphenol (meth)acrylate, phenoxy acrylate, p-tert-butyl phenyl (meth)acrylate, phenoxyethyl (meth)acrylate, phenoxypropyl (meth)acrylate, phenoxydiethylene glycol (meth)acrylate, and ethylene glycol with repeating units of 3 or more. The following are examples of phenoxy polyethylene glycol (meth)acrylates, ethylene oxide-modified nonylphenol (meth)acrylates, nonylphenoxy polyethylene glycol (meth)acrylates, nonylphenoxy polyethylene glycol-polypropylene glycol (meth)acrylates, ethylene oxide-modified cresol (meth)acrylates, phenol ethylene oxide-modified (meth)acrylates, 2-hydroxy-3-phenoxypropyl (meth)acrylate, methoxybenzyl (meth)acrylate, m-phenoxybenzyl (meth)acrylate, and (meth)acrylates (preferably 3 to 20%). Monomers containing benzyl chloride, cresol (meth)acrylate, polystyrene (meth)acrylate, 2-(meth)acryloyloxyethyl-2-hydroxyethyl phthalate, monohydroxyethyl (meth)acrylate, etc.; hydroxyethylated β-naphthol (meth)acrylate, 2-naphthyl ethyl (meth)acrylate, 2-naphthyloxyethyl (meth)acrylate, 2-(4-methoxy-1-naphthyloxy)ethyl (meth)acrylate, 1-naphthyl methyl (meth)acrylate, 2-naphthyl (meth)acrylate Monomers containing naphthyl ring units, such as methyl methacrylate and hydroxynaphthyl methacrylate; monomers containing biphenyl ring units, such as biphenyl methacrylate; monomers containing fluorene ring units, such as fluorene methacrylate, 9-fluorene methyl methacrylate (9-(meth)acryloyloxymethylfluorene), and hydroxyfluorene methacrylate; monomers containing dinaphthiophene ring units, such as 5-dinaphthiophene ethyl methacrylate, 6-dinaphthiophene ethyl methacrylate, and 6-dinaphthiophene methyl methacrylate; etc.

[0033] In addition, as monomers (a1), commercially available products such as M-101A, M-102, M-111, M-113, M-5400, and M-5700 manufactured by Toa Synthetic Co., Ltd.; Blemmer ANP-300 and 75ANEP-600 manufactured by Nippon Oil Co., Ltd.; and NK Ester AMP-20GY manufactured by Shin-Nakamura Chemical Industry Co., Ltd. can also be used.

[0034] Preferred aromatic monomers (a1) may include aralkyl esters of (meth)acrylic acid (e.g., benzyl (meth)acrylic acid, naphthyl methyl (meth)acrylic acid, etc.), or substances formed by bonding the aralkyl ester of (meth)acrylic acid with aromatic substituents (preferably aryl or aryloxy) (e.g., p-phenyl benzyl (meth)acrylic acid, phenoxy benzyl (meth)acrylic acid, etc.), aryloxyalkyl esters of (meth)acrylic acid (e.g., phenoxyethyl (meth)acrylic acid, etc.), and substances formed by bonding the aryloxyalkyl ester of (meth)acrylic acid with aromatic substituents (preferably aryl) (e.g., ethoxylated o-phenylphenol (meth)acrylic acid, etc.).

[0035] Especially as an aromatic monomer (a1). Preferably, substances comprising aralkyl esters of (meth)acrylic acid bonded with aromatic substituents (preferably aryl or aryloxy), and / or aryloxyalkyl esters of (meth)acrylic acid. More preferably, a substance comprising at least an aralkyl ester of (meth)acrylic acid bonded with an aromatic substituent (preferably aryl or aryloxy group). Further preferred are substances comprising aralkyl esters of (meth)acrylic acid bonded with aromatic substituents (preferably aryl or aryloxy), and aroxyalkyl esters of (meth)acrylic acid.

[0036] As an aralkyl ester of the (meth)acrylic acid, C(meth)acrylic acid is preferred. 6-10 Aryl C 1-4 Alkyl ester, more preferably (meth)acrylate phenyl C 1-4 Alkyl ester, (meth)acrylate naphthyl C 1-4 Alkyl esters.

[0037] As a substance formed by bonding an aromatic substituent to an aralkyl ester of the (meth)acrylic acid, the preferred embodiment is an aralkyl ester of the (meth)acrylic acid (i.e., (meth)acrylic acid C... 6-10 Aryl C 1-4 Alkyl esters, (meth)acrylate phenyl C 1-4 Alkyl ester, or (meth)acrylate naphthyl C 1-4 A substance formed by bonding an aryl group or an aryloxy group (especially an aryloxy group) to an alkyl ester, more preferably a substance formed by bonding a phenyl group or an phenoxy group (especially an phenoxy group) to an alkyl ester of the (meth)acrylic acid.

[0038] As an aryloxyalkyl ester of the (meth)acrylic acid, it is preferably a C4-hydroxyalkyl ester of (meth)acrylic acid. 6-10 Aryloxy C 1-4 Alkyl esters, more preferably phenoxy C-type (meth)acrylic acid esters. 1-4 Alkyl esters.

[0039] As a substance formed by bonding an aromatic substituent to an aryloxyalkyl ester of the (meth)acrylic acid, the preferred embodiment is the aryloxyalkyl ester of the (meth)acrylic acid (i.e., the C4 group of the (meth)acrylic acid). 6-10 Aryloxy C 1-4 alkyl esters or phenoxy C of (meth)acrylic acid 1-4 The substance formed by bonding an aryl group to an alkyl ester, or a modified alkyl oxide thereof, more preferably a substance formed by bonding an aryl group to an aryloxyalkyl ester of (meth)acrylic acid, or a modified ethylene oxide or propylene oxide thereof, and even more preferably a substance formed by bonding a phenyl group to an aryloxyalkyl ester of (meth)acrylic acid, or a modified ethylene oxide or propylene oxide thereof.

[0040] The content of aromatic structural units (A1) in 100% by mass of copolymer (A) is, for example, 40-99% by mass, preferably 50-95% by mass, and more preferably 70-90% by mass. The higher the content of aromatic structural units (A1), the higher the refractive index of the adhesive layer. In addition, the transparency of the adhesive layer is also more likely to increase.

[0041] It should be noted that the proportions of each structural unit (A1, and (A2), (A3), etc., as described below) in copolymer (A) can be determined by separating the monomer (a) in the adhesive composition from copolymer (A) using solid-liquid separation or extraction, and then performing NMR (Nuclear Magnetic Resonance) analysis on copolymer (A). Furthermore, when the proportions of monomers (a1), (a2), and (a3) ​​(specifically (a31) to (a42)) at the time of polymerization are known to be equal to the proportions of each structural unit (A1), (A2), and (A3) (specifically (A31) to (A42)) in copolymer (A), the proportions of each structural unit (A1), (A2), and (A3) (specifically (A31) to (A42)) in copolymer (A) can be determined based on the addition ratio instead of analysis.

[0042] 1.1.2 Hydroxyl-containing structural unit (A2) The hydroxyl-containing monomer (a2) that forms the hydroxyl-containing structural unit (A2) is preferably a monomer having an intramolecular hydroxyl group and a (meth)acryloyl group (wherein it does not have an aromatic hydrocarbon ring). Examples of hydroxyl-containing monomers (a2) include 4-hydroxybutyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, hydroxymethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, etc. (meth)acrylate hydroxy C 1-10Alkyl esters; polyethylene glycol mono(meth)acrylates with 2 or more repeating units (preferably 2 or more and 20 or less) and propylene glycol mono(meth)acrylates with 2 or more repeating units (preferably 2 or more and 20 or less), etc., polyC 2-4 Alkylene glycol mono(meth)acrylate; (meth)acrylate hydroxyl C 1-10 Alkyl esters modified with caprolactone; methacrylates containing hydroxyl groups and aliphatic hydrocarbon rings, such as 1,4-cyclohexanediethanol mono(meth)acrylate; and methacrylamides such as N-(2-hydroxyethyl)(meth)acrylamide, N-(2-hydroxypropyl)(meth)acrylamide, and N-(2,2-dimethyl-β-hydroxyethyl)(meth)acrylamide. Furthermore, as monomers (a2), commercially available products such as PLACEL FA1, FA1DDM, FA2, FA2D, FA3, FA4, FA5, FA10L, FM1, FM1D, FM2, FM2D, FM3, FM4, and FM5 manufactured by Daicel Corporation; and Blemmer AE-90U, AE-200, AE-400, AP-200, AP-400, AP-400D, AP-550, AP-800, and AP-1000D manufactured by Nippon Oil Co., Ltd. can also be used. These hydroxyl-containing monomers (a2) can be used alone or in combination of two or more.

[0043] From the viewpoint of good transparency, low gel content in copolymer (A), and good appearance, (meth)acrylic acid hydroxy C is preferred. 2-4 Alkyl esters, N-(hydroxyl C) 2-4 Alkyl (meth)acrylamide, PLACEL manufactured by Daicel Corporation (especially the F series), more preferably 4-hydroxybutyl (meth)acrylate, N-(2-hydroxyethyl) (meth)acrylamide, PLACEL FA1DDM, FA2D, FM1D, FM2D, FM5.

[0044] The content of the hydroxyl-containing structural unit (A2) in 100% by mass of the copolymer (A) is, for example, 1 to 40% by mass, preferably 3 to 30% by mass, and more preferably 7 to 25% by mass. A higher content of the hydroxyl-containing structural unit (A2) further enhances the affinity with the inorganic particles (B) and further improves the transparency under humidified conditions. Furthermore, a lower content of the hydroxyl-containing structural unit (A2) improves the hygrothermal durability of the adhesive composition, and enhances its adhesion and coatability.

[0045] The total content of aromatic structural units (A1) and hydroxyl-containing structural units (A2) in 100% by mass of copolymer (A) is, for example, 50-100% by mass, preferably 60-99% by mass, more preferably 75-95% by mass, and may also be 85-100% by mass or 95-100% by mass. Furthermore, the mass ratio (A1 / A2) of aromatic structural units (A1) to hydroxyl-containing structural units (A2) is, for example, 50 / 50-99 / 1, preferably 70 / 30-98 / 2, more preferably 75 / 25-95 / 5, even more preferably 80 / 20-90 / 10, and particularly preferably 83 / 17-88 / 12.

[0046] 1.1.3 Other structural units (A3) The copolymer (A) may contain structural units (A3) derived from monomers other than aromatic monomers (a1) and hydroxyl-containing monomers (a2) (hereinafter sometimes referred to as other structural units (A3) or structural units (A3)). By including other structural units (A3), the copolymer (A) can possess various properties.

[0047] The content of other structural units (A3) in 100% by mass of copolymer (A) is, for example, 0 to 50% by mass, preferably 1 to 50% by mass, more preferably 1 to 40% by mass, and even more preferably 5 to 25% by mass.

[0048] Other monomers (a3) ​​that can become other structural units (A3) include (meth)acrylate monomers containing alicyclic hydrocarbon groups (a31), (meth)acrylate monomers containing nitrogen atoms (a32), (meth)acrylate monomers containing alkoxyalkyl groups (a33), (meth)acrylate alkyl monomers with low Tg (glass transition temperature) below -20°C (a34), (meth)acrylate alkyl monomers with glass transition temperature above -20°C (a35), monomers containing acid groups (a36), and (meth)acrylate monomers having acyl or cyclic ether groups (especially epoxy groups) (a37). The monomers used include (meth)acrylate monomers with phosphate groups (a38), monomers containing sulfonic acid groups (a39), vinyl monomers with silane groups (a40), styrene monomers (a41), macromolecular monomers (a42), etc., preferably monomers (a31) to (a40), more preferably (meth)acrylate monomers containing alicyclic hydrocarbon groups (a31), (meth)acrylate monomers containing nitrogen atoms (a32), (meth)acrylate monomers containing alkoxyalkyl groups (a33), low-Tg (meth)acrylate alkyl ester monomers with a glass transition temperature of -20°C or less for homopolymers (a34), monomers containing acid groups (a36), etc. These other monomers (a3) ​​can be used alone or in combination of two or more. When using (meth)acrylate monomers containing alicyclic hydrocarbon groups (a31), the dielectric constant of the adhesive layer can be reduced. When nitrogen-containing (meth)acrylate monomers (a32) are used, hydrophilicity is improved, clouding of the adhesive layer in humidified environments is suppressed, and the adhesive strength of the adhesive layer is enhanced by increasing cohesion. When alkoxyalkyl (meth)acrylate monomers (a33) are used, the hydrophilicity of the adhesive layer is improved, and the adhesive strength of the adhesive layer is enhanced by increasing cohesion. When low-Tg (meth)acrylate monomers (a34) with a glass transition temperature below -20°C are used, the adhesive strength of the adhesive layer is enhanced by improving adhesion. When acid-containing monomers (a36) are used, the adhesive strength of the adhesive layer is enhanced by increasing cohesion.

[0049] It should be noted that the structural unit derived from the single unit (a31) is called the structural unit (A31), and similarly, the structural units derived from the single units (a32) to (a42) are called the structural units (A32) to (A42), respectively.

[0050] The (meth)acrylate monomer (a31) containing an alicyclic hydrocarbon group (sometimes simply referred to as monomer (a31)) is preferably a monomer having an alicyclic hydrocarbon ring and a (meth)acryloyl group (wherein lacking an aromatic hydrocarbon ring and a hydroxyl group) within the molecule. Examples of monomers (a31) include monocyclic monomers represented by cyclopentyl methacrylate, cyclohexyl methacrylate, and 3,3,5-trimethylcyclohexyl methacrylate, as well as bridged ring monomers such as isobornyl methacrylate, dicyclopentyl methacrylate, dicyclopentenyl methacrylate, adamantyl methacrylate, and dicyclopentenoxyethyl methacrylate; bridged ring monomers such as isobornyl methacrylate are preferred. In addition, commercially available products such as FANCRYL FA-511AS, FA-512AS, and FA-513AS manufactured by Resonac Co., Ltd. can also be used as monomers (a31).

[0051] The content of structural unit (A31) derived from the monomer (a31) is, for example, 0 to 50% by mass in 100% by mass of copolymer (A), preferably 5 to 40% by mass, and more preferably 10 to 30% by mass.

[0052] Nitrogen-containing (meth)acrylate monomers (a32) (sometimes simply referred to as monomers (a32)) are preferably monomers that have a nitrogen atom and a (meth)acryloyl group (wherein they do not have an aromatic hydrocarbon ring and a hydroxyl group) in the molecule. Examples of monomers (a32) include amino-containing monomers such as dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, N-tert-butylaminoethyl (meth)acrylate, and methacryloyloxyethyltrimethylammonium chloride; monomers containing amide groups such as N-(meth)acryloylmorpholine, N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, (meth)acrylamide, N-isopropyl(meth)acrylamide, N-tert-butyl(meth)acrylamide, and diacetone(meth)acrylamide; monomers with urethane groups such as urethane (meth)acrylate; and monomers containing imide groups such as N-(meth)acryloyloxyethylhexahydrophthalimide; etc., preferably monomers containing amide groups such as N-acryloylmorpholine. Furthermore, commercially available products such as M-140 manufactured by Toa Synthetic Co., Ltd. may also be used as monomers (a32). It should be noted that in this specification, monomers containing a nitrogen atom, a (meth)acryloyl group, and an alicyclic hydrocarbon ring (which does not contain an aromatic hydrocarbon ring and a hydroxyl group) are classified as monomers (a32).

[0053] The content of structural unit (A32) derived from the monomer (a32) is, for example, 0 to 50% by mass in 100% by mass of copolymer (A), preferably 1 to 30% by mass, and more preferably 5 to 20% by mass.

[0054] Alkoxyalkyl (meth)acrylate monomers (a33) (sometimes simply referred to as monomer (a33)) are preferably monomers having an alkoxyalkyl group and a (meth)acryloyl group (wherein lacking an aromatic hydrocarbon ring and a hydroxyl group) within the molecule. Examples of monomers (a33) include methoxyethyl methacrylate, ethoxymethyl methacrylate, ethoxyethyl methacrylate, propoxyethyl methacrylate, butoxyethyl methacrylate, methoxypropyl methacrylate, methoxybutyl methacrylate, 2-ethylhexyl methacrylate, and other alkoxyalkyl methacrylates (preferably C-methacrylate). 1-4 Alkoxy C 1-4 Alkyl esters); ethoxy-diethylene glycol (meth)acrylate, ethoxy-triethylene glycol (meth)acrylate, methoxy-triethylene glycol (meth)acrylate, methoxy-diethylene glycol (meth)acrylate, propoxy-diethylene glycol (meth)acrylate, propoxy-triethylene glycol (meth)acrylate, 2-ethylhexyl-diethylene glycol (meth)acrylate (2-ethylhexyloxy-diethylene glycol (meth)acrylate), 2-ethylhexyloxy-triethylene glycol (meth)acrylate, 2-ethylhexyloxy-polyethylene glycol (meth)acrylate with 4 or more repeating units of ethylene glycol (preferably 4 or more and 10 or less), methoxy-polyethylene glycol (meth)acrylate with 4 or more repeating units of ethylene glycol (preferably 4 or more and 25 or less, more preferably 4 or more and 10 or less), methoxy-dipropylene glycol (meth)acrylate, etc. C 1-8 Alkoxy (poly) C 2-4 Alkyl glycol (meth)acrylates; etc., preferably (meth)acrylate methoxyethyl esters, etc. (meth)acrylate C 1-4 Alkoxy C 1-4 Alkyl esters. In addition, as monomers (a33), commercially available products such as M-120 manufactured by Toa Synthetic Co., Ltd.; Blemmer AME-400 manufactured by Nippon Oil Co., Ltd.; and NKEster AM-90G, AM-130G, and AM-230G manufactured by Shin-Nakamura Chemical Industry Co., Ltd. can also be used.

[0055] The content of structural unit (A33) derived from the monomer (a33) is, for example, 0 to 50% by mass in 100% by mass of copolymer (A), preferably 5 to 40% by mass, and more preferably 10 to 30% by mass.

[0056] Homopolymers with low Tg (meth)acrylate alkyl ester monomers (a34) (sometimes simply referred to as monomer (a34)) and (meth)acrylate alkyl ester monomers (a35) (sometimes simply referred to as monomer (a35)) with glass transition temperatures below -20°C include the following examples of substances with corresponding glass transition temperatures: methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, tert-butyl methacrylate, and propyl methacrylate. Amyl acrylate, isoamyl acrylate, 2-ethylhexyl acrylate, n-hexyl acrylate, n-heptyl acrylate, n-octyl acrylate, 2-octyl acrylate, 2-ethylhexyl acrylate, n-nonyl acrylate, isononyl acrylate, n-decyl acrylate, isodecyl acrylate, n-dodecyl acrylate (n-lauryl acrylate), stearyl acrylate, isostearyl acrylate, cetyl acrylate, behenyl acrylate.

[0057] In addition, commercially available products such as Blemmer CA and VA manufactured by Nippon Oil Co., Ltd., and FANCRYL FA-111A manufactured by Resonac Co., Ltd., can also be used as monomers (a34) and (a35).

[0058] The monomer (a34) is preferably ethyl acrylate, n-propyl acrylate, n-butyl acrylate, isobutyl acrylate, n-pentyl acrylate, n-hexyl acrylate, n-octyl acrylate, 2-octyl acrylate, 2-ethylhexyl acrylate, n-nonyl acrylate, isononyl acrylate, etc., and more preferably n-butyl acrylate and 2-ethylhexyl acrylate.

[0059] The content of structural unit (A34) derived from the monomer (a34) in 100% by mass of copolymer (A) is, for example, 0 to 50% by mass, preferably 0 to 30% by mass, more preferably 1 to 20% by mass. The content of structural unit (A35) derived from the monomer (a35) in 100% by mass of copolymer (A) is, for example, 0 to 50% by mass, preferably 0 to 10% by mass, more preferably 0 to 5% by mass.

[0060] The monomer containing an acid group (a36) (sometimes simply referred to as monomer (a36)) is preferably a monomer with a carboxyl group and a polymerizable unsaturated group (which does not have an aromatic hydrocarbon ring and a hydroxyl group) in the molecule. As monomers (a36), examples include unsaturated monocarboxylic acids such as (meth)acrylic acid, cinnamic acid, crotonic acid, myristoleic acid, palmitoleic acid, and oleic acid; unsaturated dicarboxylic acids such as maleic acid, fumaric acid, itaconic acid, and citraconic acid; monoesters of unsaturated dicarboxylic acids such as monomethyl maleate, monobutyl maleate, monomethyl itaconic acid, and monobutyl itaconic acid; anhydrides of unsaturated dicarboxylic acids such as maleic anhydride, fumaric anhydride, and itaconic anhydride; monoesters of saturated dicarboxylic acids with polymerizable unsaturated groups in the ester portion, such as 2-(meth)acryloyloxyethyl succinate and 2-(meth)acryloyloxyethyl hexahydrophthalic acid; ω-carboxyl-polycaprolactone mono(meth)acrylate; etc., preferably unsaturated monocarboxylic acids, more preferably (meth)acrylic acid. In addition, commercially available monomers (a36) such as M-5300 manufactured by Toa Synthetic Co., Ltd. and NK Ester A-SA manufactured by Shin-Nakamura Chemical Co., Ltd. may also be used. It should be noted that in this specification, monomers containing a carboxyl group, a (meth)acryloyl group, and an alicyclic hydrocarbon ring (which does not contain an aromatic hydrocarbon ring and a hydroxyl group) are classified as monomers (a36).

[0061] The content of the structural unit (A36) derived from the monomer (a36) in 100% by mass of the copolymer (A) is, for example, 0 to 50% by mass, preferably 0 to 30% by mass, more preferably 0 to 10% by mass, or may be 0% by mass (i.e., acid-free).

[0062] (Meth)acrylate monomers (a37) having an acyl or cyclic ether group (sometimes simply referred to as monomer (a37)) are preferably monomers having an acyl and / or cyclic ether group and a (meth)acryloyl group (wherein lacking an aromatic hydrocarbon ring and a hydroxyl group) within the molecule. Examples of the cyclic ether group include cyclic ether groups having one ether bond such as epoxy, oxetyl, and tetrahydrofuranyl; cyclic ether groups having two ether bonds such as 1,3-dioxacyclopentyl and 1,3-dioxacyclohexyl; etc., with epoxy being preferred. That is, monomer (a37) is preferably a (meth)acrylate monomer having an acyl or epoxy group.

[0063] Examples of monomers (a37) include glycidyl methacrylate, 4-hydroxybutyl methacrylate glycidyl ether, tetrahydrofurfuryl methacrylate, cyclic trimethylolpropane acetal (meth)acrylate, methyl methacrylate (2-methyl-2-ethyl-1,3-dioxacyclopentan-4-yl) methyl methacrylate, methyl methacrylate (3-ethyloxacyclobutan-3-yl) methyl methacrylate, and 2-acetylacetoxyethyl methacrylate.

[0064] The content of the structural unit (A37) derived from the monomer (a37) is, for example, 0 to 50% by mass in 100% by mass of the copolymer (A), preferably 0 to 20% by mass, and more preferably 0 to 10% by mass.

[0065] The (meth)acrylic monomer (a38) having a phosphate group (sometimes simply referred to as monomer (a38)) is preferably a monomer having a phosphate group and / or a phosphate ester group and a polymerizable unsaturated group (wherein it does not have an aromatic hydrocarbon ring and a hydroxyl group) within the molecule. Examples of monomers (a38) include 2-methacryloyloxyethyl diphenyl phosphate (meth)acrylate, trimethacryloyloxyethyl phosphate (meth)acrylate, and triacryloyloxyethyl phosphate (meth)acrylate.

[0066] The content of the structural unit (A38) derived from the monomer (a38) is, for example, 0 to 50% by mass in 100% by mass of the copolymer (A), preferably 0 to 20% by mass, and more preferably 0 to 10% by mass.

[0067] The monomer (a39) containing a sulfonic acid group (sometimes simply referred to as monomer (a39)) is preferably a monomer having a sulfonic acid group and / or a sulfonate group and a polymerizable unsaturated group (wherein it does not have an aromatic hydrocarbon ring and a hydroxyl group) within its molecule. Examples of monomers (a39) include sodium sulfopropyl (meth)acrylate, sodium 2-sulfoethyl (meth)acrylate, and sodium 2-acrylamido-2-methylpropanesulfonate. The content of the structural unit (A39) derived from said monomer (a39) is, for example, 0 to 50% by mass in 100% by mass of the copolymer (A), preferably 0 to 20% by mass, and more preferably 0 to 10% by mass.

[0068] The silane-containing vinyl monomer (a40) (sometimes simply referred to as monomer (a40)) is preferably a monomer having an intramolecular silane and a vinyl group (wherein lacking an aromatic hydrocarbon ring and a hydroxyl group). Examples of monomers (a40) include vinyltrimethoxysilane, vinyltriethoxysilane, vinyltris(β-methoxyethyl)silane, vinyltriacetylsilane, and methacryloxypropyltrimethoxysilane. It should be noted that, in this specification, monomers having an intramolecular silane, a vinyl group, and an acyl group (wherein lacking an aromatic hydrocarbon ring and a hydroxyl group) are classified as monomers (a40).

[0069] The content of structural unit (A40) derived from the monomer (a40) is, for example, 0 to 50% by mass in 100% by mass of copolymer (A), preferably 0 to 20% by mass, and more preferably 0 to 10% by mass.

[0070] Styrene monomers (a41) (sometimes simply referred to as monomers (a41)) are preferably monomers having a styrene skeleton (wherein they do not contain hydroxyl groups). Examples of monomers (a41) include styrene, 4-tert-butylstyrene, α-methylstyrene, m-methylstyrene, p-methylstyrene, p-chlorostyrene, p-chloromethylstyrene, etc.

[0071] The content of structural unit (A41) derived from the monomer (a41) is, for example, 0 to 50% by mass in 100% by mass of copolymer (A), preferably 0 to 20% by mass, and more preferably 0 to 10% by mass.

[0072] Macromonomer (a42) (sometimes simply referred to as monomer (a42)) refers to a high molecular weight monomer having polymerizable unsaturated groups. The number-average molecular weight of monomer (a42) is not particularly limited, for example, it is 3,000 to 30,000. Monomer (a42) is preferably a macromonomer whose main component is at least one selected from (meth)acrylate, styrene monomers, and (meth)acrylonitrile; more preferably, it is a macromonomer whose main component is selected from (meth)acrylate C. 1-4 The macromonomer is composed primarily of at least one of alkyl esters, styrene, and (meth)acrylonitrile. It should be noted that the term "primary component" refers to a component constituting the macromonomer that comprises, for example, 50% or more by mass, preferably 80% or more by mass, and more preferably 90% or more by mass. Commercially available monomers such as AA-6, AS-6, AN-6S, AB-6, AW-6S, AK-5, and AK-32 manufactured by Toa Synthetic Co., Ltd. may also be used as monomer (a42).

[0073] The content of structural unit (A42) derived from the monomer (a42) is, for example, 0 to 50% by mass in 100% by mass of copolymer (A), preferably 0 to 20% by mass, and more preferably 0 to 10% by mass.

[0074] The weight-average molecular weight of copolymer (A) is, for example, 500,000 to 3,000,000, preferably 700,000 to 2,500,000, more preferably 1,000,000 to 2,000,000, and particularly preferably 1,200,000 to 1,500,000.

[0075] The refractive index of the copolymer (A) is, for example, 1.50 to 1.65, preferably 1.52 to 1.63, and more preferably 1.55 to 1.60.

[0076] The copolymer (A) can be manufactured by copolymerizing (meth)acrylate monomers (a). While the polymerization method is not particularly limited, solution polymerization using a polymerization initiator is generally employed. As the solvent for solution polymerization, one or more solvents selected from common solvents such as ethyl acetate, toluene, methyl ethyl ketone, and acetone are preferably used.

[0077] Examples of polymerization initiators include 2,2'-azobisisobutyronitrile (AIBN), 2,2'-azobis(2-methylbutyronitrile), azodicyanovalerate, 2,2'-azobis(4-methoxy-2,4-dimethylvaleritrile), 2,2'-azobis(2,4-dimethylvaleritrile), dimethyl 2,2'-azobis(2-methylpropionate), 2,2'-azobis(2-methylbutyronitrile), 1,1'-azobis(cyclohexane-1-carboxylonitrile), 2,2'-azobis[N-(2-propenyl)-2-methylpropionamide], 2,2'-azobis(N-butyl-2-methylpropionamide), 2,2'-azobis[2-(2-imidazoline-2-yl)propane] dihydrochloride, 2,2'-azobis[2-(2-imidazoline-2-yl)propane] dihydrochloride, and 2,2'-azobis[2-(2-imidazoline-2-yl)propane] dihydrochloride. Azo compounds include: 2,2'-azobis(2-methylpropane)dihydrate, 2,2'-azobis[N-(2-carboxyethyl)-2-methylpropane]hydrate, 2,2'-azobis[2-(2-imidazoline-2-yl)propane], 2,2'-azobis(1-imino-1-pyrrolyl-2-methylpropane)dihydrochloride, 2,2'-azobis[2-methyl-N-(2-hydroxyethyl)propamide], etc.; organic peroxides such as tert-butyl peroxypentanoate, tert-butyl peroxybenzoate, tert-butyl peroxy-2-ethylhexanoate, di-tert-butyl peroxide, cumene hydroperoxide, benzoyl peroxide, tert-butyl hydroperoxide, etc.; and inorganic peroxides such as hydrogen peroxide, ammonium persulfate, potassium persulfate, sodium persulfate, etc. These polymerization initiators can be used alone or in combination of two or more.

[0078] Chain transfer agents can also be used in copolymerization reactions. Examples of chain transfer agents include thiols such as methyl mercaptan, tert-butyl mercaptan, decyl mercaptan, benzyl mercaptan, stearyl mercaptan, n-dodecyl mercaptan, tert-dodecyl mercaptan, mercaptoacetic acid, mercaptopropionic acid and its esters (such as 2-ethylhexyl 3-mercaptopropionic acid), 2-ethylhexyl thioglycol, and octyl mercaptoacetate; alcohols such as methanol, ethanol, propanol, n-butanol, isopropanol, tert-butanol, hexanol, benzyl alcohol, and allyl alcohol; halogenated hydrocarbons such as chloroethane, fluoroethane, and trichloroethylene; carbonyl groups such as acetone, methyl ethyl ketone, cyclohexanone, acetophenone, acetaldehyde, propionaldehyde, n-butyraldehyde, furfural, and benzaldehyde; methyl-4-cyclohexene-1,2-dicarboxylic anhydride; and α-methylstyrene. These chain transfer agents can be used alone or in combination of two or more.

[0079] The temperature and time of the copolymerization reaction can be appropriately combined, for example, within the range of 40°C to 90°C and 1 to 10 hours. It should be noted that under these conditions, the copolymerization reaction may sometimes continue until the amount of residual monomer (a) after polymerization is insufficient. For example, if a combination of reaction temperature above 50°C and reaction time above 5 hours is selected, the copolymerization reaction may sometimes continue until the amount of residual monomer (a) is as low as less than 7% by mass in 100% of the total copolymer (A) and residual monomer (a). In this case, the adhesive composition of the present invention can be prepared simply by adding monomer (a) after the reaction is complete. Preferred reaction conditions are those that leave a necessary amount of residual monomer (a) and are capable of producing copolymer (A), for example, a combination of reaction temperature below 70°C and reaction time below 2 hours selected from the above range. Under these conditions, a necessary amount of monomer (a) can be retained, eliminating the need to add monomer (a) after the reaction is complete.

[0080] 1.2 (Meth)acrylate monomers (a) The adhesive composition, as described above, comprises a (meth)acrylate monomer (a). By including the (meth)acrylate monomer (a), the dispersibility of the inorganic particles (B) can be improved, and the transparency of the adhesive layer can be enhanced. The (meth)acrylate monomer (a) can be a residue of unreacted monomer (a) used during the polymerization of the (meth)acrylate copolymer (A) (so-called residual monomer), or it can be a monomer (a) added after the reaction. However, from the viewpoint of simplifying the addition process and increasing the molecular weight of the (meth)acrylate copolymer (A), a residual monomer is preferred.

[0081] When monomer (a) in the adhesive composition is a residual monomer, the monomer (a1) that becomes a structural unit (A1) is identical to the monomer (a1) in the adhesive composition. Similarly, the monomer (a2) that becomes a structural unit (A2) is identical to the monomer (a2) in the adhesive composition, and the monomer (a3) ​​that becomes a structural unit (A3) is identical to the monomer (a3) ​​in the adhesive composition.

[0082] The content of monomer (a) is, for example, 7 to 30% by mass, preferably 8 to 25% by mass, and more preferably 10 to 20% by mass, in 100% by mass of the total copolymer (A) and said monomer (a). By making the amount of monomer (a) appropriate, the adhesive layer can still exhibit excellent transparency even if the thickness of the adhesive layer increases.

[0083] As monomers (a), they include aromatic monomers (a1), hydroxyl-containing monomers (a2), etc., and other monomers (a3) ​​may be included as needed. Specific examples and preferred examples are the same as those described for the copolymer (A) above. The content of each monomer in 100% by mass of the total monomers (a) in the adhesive composition is as follows, for example.

[0084] The content of aromatic monomers (a1) is, for example, 40 to 99% by mass, preferably 50 to 95% by mass, and more preferably 70 to 90% by mass.

[0085] The content of the hydroxyl-containing monomer (a2) is, for example, 1 to 40% by mass, preferably 3 to 30% by mass, and more preferably 7 to 25% by mass.

[0086] The content of other monomers (a3) ​​is, for example, 0 to 50% by mass, preferably 1 to 50% by mass, more preferably 1 to 40% by mass, and even more preferably 5 to 25% by mass.

[0087] The content of (meth)acrylate monomers (a31) containing alicyclic hydrocarbon groups is, for example, 0 to 50% by mass, preferably 5 to 40% by mass, and more preferably 10 to 30% by mass.

[0088] The content of nitrogen-containing (meth)acrylate monomers (a32) is, for example, 0 to 50% by mass, preferably 1 to 30% by mass, and more preferably 5 to 20% by mass.

[0089] The content of alkoxyalkyl (meth)acrylate monomers (a33) is, for example, 0 to 50% by mass, preferably 5 to 40% by mass, and more preferably 10 to 30% by mass.

[0090] The content of low Tg (meth)acrylate alkyl ester monomers (a34) with a glass transition temperature of -20°C or below in the homopolymer is, for example, 0 to 50% by mass, preferably 0 to 30% by mass, and more preferably 1 to 20% by mass.

[0091] The content of (meth)acrylate alkyl ester monomers (a35) with a glass transition temperature exceeding -20°C is, for example, 0 to 50% by mass, preferably 0 to 10% by mass, and more preferably 0 to 5% by mass.

[0092] The content of the acid-containing monomer (a36) is, for example, 0 to 50% by mass, preferably 0 to 30% by mass, more preferably 0 to 10% by mass, or 0% by mass.

[0093] The content of (meth)acrylate monomers (a37) having acyl or epoxy groups is, for example, 0 to 50% by mass, preferably 0 to 20% by mass, and more preferably 0 to 10% by mass.

[0094] The content of (meth)acrylic monomers (a38) with phosphate groups is, for example, 0 to 50% by mass, preferably 0 to 20% by mass, and more preferably 0 to 10% by mass.

[0095] The content of the sulfonic acid group-containing monomer (a39) is, for example, 0 to 50% by mass, preferably 0 to 20% by mass, and more preferably 0 to 10% by mass.

[0096] The content of the silane-containing vinyl monomer (a40) is, for example, 0 to 50% by mass, preferably 0 to 20% by mass, and more preferably 0 to 10% by mass.

[0097] The content of styrene monomers (a41) is, for example, 0 to 50% by mass, preferably 0 to 20% by mass, and more preferably 0 to 10% by mass.

[0098] The content of macromonomer (a42) is, for example, 0 to 50% by mass, preferably 0 to 20% by mass, and more preferably 0 to 10% by mass.

[0099] The total content of aromatic monomer (a1) and hydroxyl-containing monomer (a2) in the adhesive composition is, for example, 50-100% by mass of monomer (a), preferably 60-99% by mass, more preferably 75-95% by mass, or possibly 85-100% by mass or 95-100% by mass. Furthermore, the mass ratio (a1 / a2) of aromatic monomer (a1) to hydroxyl-containing monomer (a2) is, for example, 50 / 50-99 / 1, preferably 70 / 30-98 / 2, more preferably 75 / 25-95 / 5, even more preferably 80 / 20-90 / 10, and particularly preferably 83 / 17-88 / 12.

[0100] It should be noted that the proportions of monomers (a1), (a2), and (a3) ​​(specifically (a31) to (a42)) in monomer (a) of the adhesive composition can be determined by separating monomer (a) from copolymer (A) through solid-liquid separation, extraction, etc., and then analyzing the separated material using gas chromatography, NMR, etc. Furthermore, if monomer (a) is a residual monomer, and the proportions of monomers (a1), (a2), and (a3) ​​(specifically (a31) to (a42)) at the time of polymerization are known to be equal to the proportions of the residual monomers, the proportions of monomers (a1), (a2), and (a3) ​​(specifically (a31) to (a42)) in the adhesive composition can be determined based on the addition ratio instead of analysis.

[0101] 1.3 Inorganic particles (B) The adhesive composition contains inorganic particles (B). By including inorganic particles (B), the refractive index of the adhesive layer can be increased, making it suitable for use as an adhesive for optical films.

[0102] Examples of inorganic particles (B) include aluminum oxide, titanium oxide, zirconium oxide (zirconia), indium oxide, zinc oxide, tin oxide, lanthanum oxide, yttrium oxide, cerium oxide, magnesium oxide, niobium oxide, tantalum oxide, indium tin oxide, antimony tin oxide, barium titanate, strontium titanate, perovskite, and spinel, with aluminum oxide, titanium oxide, zirconium oxide, and zinc oxide being preferred, and zirconium oxide being more preferred. One or more of these particles may be used.

[0103] Inorganic particles (B) are preferably coated with a coating agent such as a carboxylic acid compound. Examples of carboxylic acid compounds include: Straight-chain saturated aliphatic carboxylic acids such as oxalic acid, malonic acid, butyric acid, succinic acid, valeric acid, glutaric acid, hexanoic acid, adipic acid, heptanoic acid, octanoic acid, nonanoic acid, decanoic acid, dodecanoic acid, tetradecanoic acid, palmitic acid, and stearic acid. Branched saturated aliphatic carboxylic acids such as neopentanoic acid, 2,2-dimethylbutyric acid, 3,3-dimethylbutyric acid, 2,2-diethylbutyric acid, 3,3-diethylbutyric acid, 2-ethylhexanoic acid, 2-methylheptanoic acid, 4-methyloctanoic acid, and neodecanoic acid. Carboxylic acids containing alicyclic hydrocarbon groups, such as cycloalkanoic acids and cyclohexanedicarboxylic acid; Acrylic acid, methacrylic acid, maleic acid, fumaric acid, oleic acid, linoleic acid, linolenic acid and other straight-chain unsaturated aliphatic carboxylic acids; Carboxylic acids containing ether bonds, such as methoxyacetic acid, ethoxyacetic acid, 3-ethoxypropionic acid, 2-methoxyethoxyacetic acid, and 2-methoxyethoxyethoxyacetic acid; Lactic acid, malic acid, citric acid, hydroxystearic acid, and other carboxylic acids containing hydroxyl groups; Pyruvic acid and other carboxylic acids containing carbonyl groups; Aromatic carboxylic acids such as benzoic acid, phthalic acid, and isophthalic acid; 2-Acryloyloxyethyl succinic acid, 2-methacryloyloxyethyl succinic acid, 2-acryloyloxyethyl hexahydrophthalic acid, 2-methacryloyloxyethyl hexahydrophthalic acid, 2-acryloyloxyethyl phthalic acid, 2-methacryloyloxyethyl phthalic acid, and other carboxylic acids containing (meth)acryloyl groups; etc.

[0104] The inorganic particles (B) are preferably coated with carboxylic acid compounds (especially monocarboxylic acid compounds) having a total carbon number of 6 or more (preferably 7 or more), and more preferably with branched saturated aliphatic carboxylic acids (especially monocarboxylic acid compounds) having a total carbon number of 6 or more (preferably 7 or more). Furthermore, the inorganic particles (B) are preferably coated with two or more carboxylic acid compounds, preferably with at least branched saturated aliphatic carboxylic acids having a total carbon number of 6 or more (preferably 7 or more), and also with carboxylic acids containing ether bonds.

[0105] As a branched saturated aliphatic carboxylic acid, it is preferred to be a branched saturated aliphatic carboxylic acid with a total carbon number of 9 or less, more preferably a branched saturated aliphatic carboxylic acid with a total carbon number of 8 or less, and particularly preferably 2-ethylhexanoic acid.

[0106] As a carboxylic acid containing an ether bond, methoxyacetic acid, ethoxyacetic acid, 3-ethoxypropionic acid, 2-methoxyethoxyacetic acid, and 2-methoxyethoxyethoxyacetic acid are preferred, more preferably methoxyacetic acid and ethoxyacetic acid, and even more preferably methoxyacetic acid.

[0107] The refractive index of the inorganic particles (B) is, for example, 1.60 to 2.72 (titanium dioxide rutile type), preferably 1.65 to 2.50, and more preferably 1.70 to 2.20.

[0108] The volume average particle size of the inorganic particles (B) is, for example, 1–100 nm, preferably 3–30 nm, and more preferably 5–20 nm. The smaller the volume average particle size, the more difficult it is to disperse the inorganic particles (B), but on the other hand, the higher the transparency when dispersion is successful. It should be noted that the volume average particle size of the inorganic particles (B) can be determined based on dynamic light scattering.

[0109] Furthermore, the number-average particle size of the inorganic particles (B) is, for example, 1 to 100 nm, preferably 3 to 30 nm, and even more preferably 5 to 20 nm. It should be noted that the number-average particle size of the inorganic particles (B) can be determined by measuring the length of the long axis of any 100 inorganic particles (B) using an electron microscope and calculating its average value.

[0110] In the particle size determination of inorganic particles (B) using dynamic light scattering, the ratio of the cumulative 90% particle size D90 to the cumulative 50% particle size D50 (D90 / D50) on a volume basis is, for example, 3.0 or less, preferably 2.5 or less, and more preferably 2.0 or less. The smaller the D90 / D50 ratio, the easier it is to uniformly disperse the inorganic particles (B).

[0111] When the inorganic particles (B) are zirconium oxide, the half-width at half-maximum (WWHM) of the (101) plane is preferably 1.20° or less when measured by XRD (X-ray diffraction) using CuKα rays as the light source. By setting the WWHM to 1.20° or less, the grain diameter increases, which improves the refractive index. The WWHM is preferably 0.6° to 1.1°, more preferably 0.65° to 1.0°, and even more preferably 0.7° to 1.0°. By setting the WWHM to 0.6° or more, the transparency of the adhesive layer can be further improved.

[0112] When the inorganic particles (B) are coated zirconium oxide, the refractive index of the zirconium oxide particles is preferably 1.7 or higher, more preferably 1.8 to 2.2, and even more preferably 1.8 to 1.9.

[0113] The amount of inorganic particles (B) in the adhesive composition relative to 100 parts by weight of copolymer (A) is, for example, 20 to 2000 parts by weight, preferably 50 to 1500 parts by weight, more preferably 80 to 1000 parts by weight, even more preferably 80 to 850 parts by weight, and may also be 80 to 700 parts by weight or 80 to 350 parts by weight. By adjusting the proportion of inorganic particles (B) within the above range, it is easier to balance refractive index and transparency.

[0114] The total content of the copolymer (A), monomer (a), and inorganic particles (B) in the adhesive composition is preferably 80-100% by mass of 100% by weight of the solids component of the adhesive composition, more preferably 90-99.9% by mass, and even more preferably 95-99.9% by mass. It should be noted that, in this specification, solids component refers to the component after the solvent has been removed.

[0115] 1.4 Silane Coupling Agent (C) The adhesive composition preferably further contains a silane coupling agent (C). The presence of a silane coupling agent (C) improves the durability of the adhesive layer and enhances the adhesion between the adhesive layer and the substrate (especially glass).

[0116] Examples of silane coupling agents (C) include silane coupling agents (especially di- or trialkoxysilanes) having reactive groups such as epoxy (glycidoxy), polymerizable groups (vinyl, (meth)acryloyl, etc.), amino, mercapto, halogen atoms, and isocyanate groups, as well as silane coupling agents (especially di- or trialkoxysilanes) having hydrocarbon groups. Silane coupling agents with reactive groups are preferred, and silane coupling agents with epoxy (glycidoxy) groups are more preferred.

[0117] Examples of epoxy-containing silane coupling agents (C1) include 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, γ-glycidoxypropyltrimethoxysilane, and γ-glycidoxypropyltriethoxysilane.

[0118] Examples of silane coupling agents (C2) with polymerizable groups include vinyltrichlorosilane, vinyltrimethoxysilane, vinyltriethoxysilane, vinyltri(β-methoxyethoxy)silane, γ-methacryloxypropylmethyldimethoxysilane, γ-methacryloxypropyltrimethoxysilane, γ-methacryloxypropylmethyldiethoxysilane, γ-methacryloxypropyltriethoxysilane, and γ-acryloxypropyltrimethoxysilane.

[0119] Examples of amino-containing silane coupling agents (C3) include N-β-(aminoethyl)-γ-aminopropylmethyldimethoxysilane, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, N-β-(aminoethyl)-γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, and N-phenyl-γ-aminopropyltrimethoxysilane.

[0120] Examples of silane coupling agents (C4) with thiol groups include γ-mercaptopropyltrimethoxysilane, γ-mercaptopropylmethyldimethoxysilane, and bis-(3-[triethoxysilyl]propyl)tetrasulfide.

[0121] Examples of silane coupling agents (C5) having halogen atoms (especially halogenated hydrocarbon groups) include γ-chloropropyltrimethoxysilane.

[0122] Examples of silane coupling agents (C6) with hydrocarbon groups include methyltrimethoxysilane, dimethyldimethoxysilane, trimethylmethoxysilane, n-propyltrimethoxysilane, ethyltrimethoxysilane, diethyldiethoxysilane, n-butyltrimethoxysilane, n-hexyltriethoxysilane, n-octyltrimethoxysilane, phenyltrimethoxysilane, diphenyldimethoxysilane, and cyclohexylmethyldimethoxysilane.

[0123] The silane coupling agent (C) may also be a combination of two silane coupling agents or their reactants, in which the reactive groups react with each other. Alternatively, a compound with hydrolyzable silane groups may be obtained by reacting other coupling agents, polyisocyanates, etc., onto the reactive groups of a silane coupling agent having reactive groups.

[0124] The silane coupling agent (C) can be obtained from Shin-Etsu Chemical Industry Co., Ltd., for example, in the form of KBM-303, KBM-403, KBE-402, KBE-403, KBE-502, KBE-503, KBM-5103, KBM-573, KBM-802, KBM-803, KBE-846, KBE-9007, etc.

[0125] The silane coupling agent (C) can be used alone or in combination of two or more.

[0126] The amount of silane coupling agent (C) in the adhesive composition is, for example, 0 to 5 parts by mass or 0.001 to 5 parts by mass relative to 100 parts by mass of copolymer (A), preferably 0.001 to 4 parts by mass, and more preferably 0.01 to 3 parts by mass. A higher content of silane coupling agent (C) improves the durability of the adhesive layer. Furthermore, by avoiding an excess of silane coupling agent (C), thermal foaming originating from low molecular weight compounds can be suppressed.

[0127] 1.5 Crosslinking agent (D) The adhesive composition preferably further contains a crosslinking agent (D). The crosslinking agent (D) can react with the copolymer (A) to form a crosslinked structure, which can improve the adhesion (bonding) of the adhesive layer and improve its durability.

[0128] Examples of crosslinking agents (D) include isocyanate compounds (D1), carbodiimide compounds (D2), oxazoline compounds (D3), epoxy compounds (D4), polyfunctional (meth)acrylate monomers (D5), polyfunctional allyl monomers (D6), and peroxides (D7). One or more of these can be used. When combining two or more, two or more crosslinking agents of the same system can be combined (e.g., two isocyanate compounds (D1)), or one or more crosslinking agents of different systems can be combined (e.g., one isocyanate compound (D1) and one peroxide (D7)).

[0129] Examples of isocyanate compounds (D1) include dimer diisocyanates, 2,4-toluene diisocyanate (2,4-TDI), 2,6-toluene diisocyanate (2,6-TDI), 4,4'-diphenylmethane diisocyanate (4,4'-MDI), 2,4'-diphenylmethane diisocyanate (2,4'-MDI), 1,4-phenylene diisocyanate, phenylene diisocyanate (XDI), tetramethylphenylene diisocyanate (TMXDI), benzyl toluidine diisocyanate (TODI), and 1,5-naphthalene diisocyanate (NDI). Aromatic diisocyanates; aliphatic diisocyanates such as allyl isocyanate, hexamethylene diisocyanate (HDI), trimethylhexamethylene diisocyanate (TMHDI), lysine diisocyanate, and norbornane diisocyanate methyl (NBDI); alicyclic diisocyanates such as transcyclohexane-1,4-diisocyanate, isophorone diisocyanate (IPDI), H6-XDI (hydrogenated XDI), and H12-MDI (hydrogenated MDI); carbodiimide-modified diisocyanates of the above diisocyanates; or isocyanurate-modified diisocyanates thereof; etc. It is also applicable to the adducts of the above isocyanate compounds (D1) with polyols such as trimethylolpropane, polytetramethylene ether glycol (PTMG), and polypropylene glycol (PPG); and the biuret and isocyanurate forms of these isocyanate compounds (D1).

[0130] Isocyanate compounds (D1) are available from Tosoh Corporation in the form of Coronate (registered trademark) L, Coronate HL, Coronate HX, Coronate 2030, Coronate 2031, etc.; from Mitsui Chemicals Corporation in the form of Takenate (registered trademark) D-102, Takenate D-110N, Takenate D-200, Takenate D-202, etc.; and from Duranate (registered trademark) 24A-100, Duranate TPA-100, Duranate TKA-100, Duranate P301-75E, Duranate E402-90T, Duranate E405-80T, Duranate TSE-100, Duranate D-101, Duranate, etc. It can be obtained from Asahi Kasei Corporation in the form of D-201, etc.; it can be obtained from Sumika Covestro Urethane Corporation in the form of Sumidur (registered trademark) N-75, N-3200, N-3300, etc.; it can be obtained from Sanyo Chemical Industry Co., Ltd. in the form of Sanprene (registered trademark, the same below) P-6090 (PTMG / MDI series), Sanprene P-663L (PTMG / TDI series), Sanprene P-664 (PTMG / TDI series), Sanprene P-665 (PTMG / TDI series), Sanprene P-667 (PTMG / TDI series), Sanprene P-868 (PTMG / HMDI series), Sanprene P-870 (PTMG / HMDI series), Sanprene C-810 (PPG / TDI series), etc.

[0131] The isocyanate compound (D1) is preferably used in its uncapped form, but it can also be a capped isocyanate compound obtained by reacting with a capping agent that protects the isocyanate group. Examples of capped isocyanate compounds include Duranate MF-B60X (capped 1,6-hexamethylene diisocyanate) and Duranate MF-K60X (capped 1,6-hexamethylene diisocyanate) manufactured by Asahi Kasei Corporation; Coronate AP-M, 2503, 2507, 2513, 2515, and Millionate (registered trademark) MS-50 manufactured by Tosoh Corporation; and Takenate manufactured by Mitsui Chemicals Co., Ltd. B-830 (terminated toluene diisocyanate), B-815N (terminated 4,4'-methylene bis(cyclohexyl isocyanate)), B-842N (terminated 1,3-bis(isocyanatomethyl)cyclohexane), B-846N (terminated 1,3-bis(isocyanatomethyl)cyclohexane), B-874N (terminated isophorone diisocyanate), B-882N (terminated 1,6-hexamethylene diisocyanate), etc.; DIC Corporation The products include Burnock (registered trademark) D-500 (terminated toluene diisocyanate) and D-550 (terminated 1,6-hexamethylene diisocyanate), manufactured by Daiichi Kogyo Pharmaceutical Co., Ltd.; and Elastron (registered trademark) BN-P17 (terminated 4,4'-diphenylmethane diisocyanate), BN-04, BN-08, BN-44, and BN-45 (all of which are terminated urethane-modified polyisocyanates), manufactured by Daiichi Kogyo Pharmaceutical Co., Ltd. Duranat MF-K60X is the preferred choice.

[0132] As the carbodiimide compound (D2), for example, a high molecular weight polycarbodiimide generated by decarbonating condensation of diisocyanate (D22) in the presence of a carbodiimide catalyst (D21) can be used. Examples of diisocyanates (D22) supplied for the decarbonating condensation reaction include 4,4'-diphenylmethane diisocyanate, 3,3'-dimethoxy-4,4'-diphenylmethane diisocyanate, 3,3'-dimethyl-4,4'-diphenylmethane diisocyanate, 4,4'-diphenyl ether diisocyanate, 3,3'-dimethyl-4,4'-diphenyl ether diisocyanate, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 1-methoxyphenyl-2,4-diisocyanate, isophorone diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, tetramethylphenyldimethyl diisocyanate, etc.

[0133] Examples of carbodiimide catalysts (D21) used in the decarbonation condensation reaction include 1-phenyl-2-phosphacyclopentene-1-oxide, 3-methyl-2-phosphacyclopentene-1-oxide, 1-ethyl-3-methyl-2-phosphacyclopentene-1-oxide, 1-ethyl-2-phosphacyclopentene-1-oxide, or their 3-phosphacyclopentene isomers, etc., phosphacyclopentene oxides, etc.

[0134] As an oxazoline compound (D3), a polymer containing an oxazoline group is preferred. Examples include acrylic / styrene polymers containing an oxazoline group whose main chain comprises an acrylic backbone and a styrene backbone and whose side chains of the main chain have oxazoline groups; and acrylic polymers containing an oxazoline group whose main chain comprises an acrylic backbone and whose side chains of the main chain have oxazoline groups.

[0135] Examples of oxazoline groups include 2-oxazoline, 3-oxazoline, and 4-oxazoline, with 2-oxazoline being preferred. Furthermore, the polymer containing the oxazoline group may also contain polyoxyalkylene groups in addition to the oxazoline group.

[0136] Examples of oxazoline compounds (D3) include Epocros (registered trademark) WS-300, Epocros (registered trademark) WS-500, and Epocros (registered trademark) WS-700 manufactured by Nippon Shokubai Co., Ltd.; and Epocros (registered trademark) K-1000 series and Epocros (registered trademark) K-2000 series manufactured by Nippon Shokubai Co., Ltd., which are acrylic / styrene polymers containing oxazoline groups.

[0137] As the epoxy compound (D4), known epoxy crosslinking agents can be used, such as "TETRAD-C" and "TETRAD-X" manufactured by Mitsubishi Gas Chemical Co., Ltd.; "Adeka Resin EPU series" and "Adeka Resin EPR series" manufactured by ADEKA Co., Ltd.; and liquid epoxy resins such as "Celloxide" manufactured by Daicel Co., Ltd. These liquid epoxy resins are preferred because they facilitate mixing during the manufacture of adhesive compositions.

[0138] The polyfunctional (meth)acrylate monomer (D5) is a (meth)acrylate monomer having multiple (two or more) (meth)acryloyl groups. Hereinafter, a (meth)acrylate monomer having N (meth)acryloyl groups in one molecule is sometimes referred to as an N-functional monomer. Examples of such (meth)acrylate monomers include hydrocarbon polyfunctional monomers (D51) or hydrocarbon ether polyfunctional monomers (D52). The hydrocarbon or hydrocarbon ether polyfunctional monomers (D51) (D52) are preferably compounds in which the hydroxyl groups of a polyol with a hydrocarbon or hydrocarbon ether group having 10 or more and 100 or fewer carbon atoms are esterified with (meth)acrylate. This compound is preferred from the viewpoint of improving adhesion (adhesion) through crosslinking. Examples of the hydrocarbon groups of the polyol include straight-chain or branched aliphatic hydrocarbon groups, aromatic hydrocarbon groups, alicyclic hydrocarbon groups, and hydrocarbon groups formed by combining these hydrocarbon groups. Examples of the hydrocarbon ether groups are substances formed by etherification of the hydrocarbon groups. Furthermore, examples of polyols with a hydrocarbon ether group as the main skeleton include compounds formed by adding alkylene oxides with 2 or more but less than 4 carbon atoms (addition number 1 or more but less than 30). Also, examples include polyalkylene glycols (addition number 1 or more but less than 30) obtained from alkylene oxides with 2 or more but less than 4 carbon atoms.

[0139] Examples of difunctional monomers (D511) among the aforementioned multifunctional hydrocarbon monomers (D51) include dimethacrylates of alkylene glycols such as ethylene glycol dimethacrylate, 1,3-butanediol dimethacrylate, 1,4-butanediol dimethacrylate, 1,6-hexanediol dimethacrylate, and neopentyl glycol dimethacrylate; dimethacrylates of diols containing alicyclic hydrocarbon groups such as cyclohexanediethanol dimethacrylate and tricyclodecanediethanol dimethacrylate (dihydroxymethyl-tricyclodecanediacrylate); dimethacrylates of diols containing aromatic hydrocarbon groups such as bisphenol A dimethacrylate; and so on.

[0140] As a difunctional monomer (D521) among the polyfunctional monomers (D52) of hydrocarbon ethers, examples include alkoxylated hexanediol di(meth)acrylate, alkoxylated cyclohexanediethanol di(meth)acrylate, alkoxylated di(meth)acrylate, alkoxylated neopentyl glycol di(meth)acrylate, alkoxylated bisphenol A di(meth)acrylate, etc., which are di(meth)acrylates of compounds formed by the addition of alkylene glycols and diols to epoxides as described in the above-mentioned difunctional monomers (D511) of hydrocarbons. Furthermore, more specific examples of difunctional monomers (D521) of hydrocarbon ethers include di(meth)acrylates of polyalkylene glycols such as diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, etc., as well as di(meth)acrylates of di(meth)acrylates of di(meth)acrylates of polyalkylene glycols such as di(meth)acrylates of ...

[0141] Examples of trifunctional to hexafunctional monomers among the multifunctional monomers (D51) (D52) of hydrocarbons or hydrocarbon ethers include, for example, trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, glycerol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, trimethylolpropane tetra(meth)acrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, etc., which are tri(meth)acrylate, tetra(meth)acrylate, penta(meth)acrylate, or hexa(meth)acrylate of tri(meth)acrylate, tetra(meth)acrylate, penta(meth)acrylate, or hexa(meth)acrylate of compounds formed by the addition of these tri(meth)acrylate, tetra(meth)acrylate, penta(meth)acrylate, or hexa(meth)acrylate to epoxides.

[0142] The polyfunctional (meth)acrylate monomer (D5) can be any (meth)acrylate monomer having multiple (two or more) (meth)acryloyl groups, or it can be a monomer other than the aforementioned hydrocarbon or hydrocarbon ether polyfunctional monomers (D51) (D52). Examples of such monomers include polyester poly(meth)acrylates and epoxy (meth)acrylates having two or more (meth)acryloyl groups at the end.

[0143] Among these polyfunctional (meth)acrylate monomers (D5), polyfunctional monomers (D51) and / or polyfunctional monomers (D52) are preferred, and polyfunctional monomers (D51) and / or polyfunctional monomers (D52) that are trifunctional to hexafunctional monomers are more preferred.

[0144] A polyfunctional allyl monomer (D6) is a monomer having at least one allyl group and having multiple (two or more) radical polymerizable functional groups, including the allyl group. Examples of such monomers include allyl methacrylate, diallyl phthalate (DAP), trimethylolpropane diallyl ether, pentaerythritol triallyl ether, and triallyl isocyanurate.

[0145] From the viewpoint of productivity and stability, the peroxide (D7) preferably has a half-life temperature of 80–160°C (1 minute), more preferably 80–140°C, even more preferably 80–125°C, and particularly preferably 90–125°C. "Half-life of the peroxide" refers to the time required for half of the peroxide to remain, and can be referenced from manufacturer catalog values, such as those listed in the 9th edition of the Organic Peroxides Catalog published by Nippon Oil Co., Ltd. (May 2003).

[0146] Examples of peroxides (D7) include diisopropyl peroxide (1-minute half-life temperature 88.3°C; temperatures in parentheses below indicate 1-minute half-life temperature), di(2-ethylhexyl) peroxide (90.6°C), bis(4-tert-butylcyclohexyl) peroxide (92.1°C), disec-butyl peroxide (92.4°C), tert-butyl peroxyneodecanate (103.5°C), tert-hexyl peroxynepentanoate (109.1°C), and tert-butyl peroxynepentanoate (1...). Examples of peroxides include dilauroyl peroxide (10.3℃), dilauroyl peroxide (116.4℃), bis(n-octanoyl) peroxide (117.4℃), 1,1,3,3-tetramethylbutyl peroxide-2-ethylhexanoate (124.3℃), di(4-methylbenzoyl) peroxide (128.2℃), dibenzoyl peroxide (benzoyl peroxide) (130.0℃), a mixture of dibenzoyl peroxide, benzoyl peroxide-m-methylbenzoyl, and m-toluyl peroxide (131.1℃), and tert-butyl peroxide-butyrate (136.1℃). Among these, diisopropyl peroxide, bis(4-tert-butylcyclohexyl) peroxide, and tert-butyl peroxide-neodecanate are preferred. These can be used individually or in combination of two or more. As a combination of two or more, a combination of bis(4-tert-butylcyclohexyl) peroxide and dilauroyl peroxide is preferred.

[0147] Peroxides (D7) can be marketed under trade names such as: "Peroyl IB" (85.1℃), "Percumyl ND" (94.0℃), "Peroyl NPP" (94.0℃), "Peroyl IPP" (88.3℃), "Peroyl SBP" (92.4℃), "Perocta ND" (92.4℃), "Peroyl TCP" (92.1℃), "Peroyl OPP" (90.6℃), "Perhexyl ND" (100.9℃), "Perbutyl ND" (103.5℃), "Perbutyl NHP" (104.6℃), "Perhexyl PV" (109.1℃), "Perbutyl PV" (110.3℃), "Peroyl 355" (112.6℃), and "Peroyl..." L (116.4℃), "Perocta O" (124.3℃), "Peroyl SA" (131.8℃), "Perhexa (registered trademark, same below) 25O" (118.8℃), "Perhexyl O" (132.6℃), "NYPER (registered trademark, same below) PMB" (128.2℃), "Perbutyl O" (134.0℃), "NYPERBMT" (131.1℃), "NYPER BW" (130.0℃), "NYPER BMT-K40" (131.1℃), "NYPER BMT-M" (131.1℃), "Perhexa MC" (142.1℃), "Perhexa TMH" (147.1℃), "Perhexa HC" (149.2℃), "Perhexa C" (153.8℃), "Pertetra (registered trademark, same below) A" (153.8℃), "Perhexyl Perbutyl I (155.0℃), Perbutyl L (159.4℃), Perbutyl I (158.8℃), Perhexa 25Z (158.2℃), Perbutyl A (159.9℃), and Perhexa 22 (159.9℃) are obtained from Nippon Oil Co., Ltd.

[0148] The amount of crosslinking agent (D) in the adhesive composition is, for example, 0.01 to 5 parts by weight relative to 100 parts by weight of copolymer (A), more preferably 0.02 to 4 parts by weight, even more preferably 0.03 to 3 parts by weight, and particularly preferably 0.05 to 2 parts by weight. When the content of crosslinking agent (D) is within the said range, durability can be further improved.

[0149] 1.6 Solvent (E) The adhesive composition may include a solvent (E). Including a solvent (E) can significantly improve coating productivity. Examples of solvents (E) include esters such as ethyl acetate and n-butyl acetate; aromatic hydrocarbons such as toluene and benzene; aliphatic hydrocarbons such as n-hexane and n-heptane; alicyclic hydrocarbons such as cyclohexane and methylcyclohexane; ketones such as methyl ethyl ketone, methyl isobutyl ketone, and acetone; glycol ethers such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, propylene glycol monomethyl ether, diethylene glycol monomethyl ether, and ethylene glycol dimethyl ether; and other organic solvents. These solvents can be used alone or in combination of two or more.

[0150] The amount of solvent (E) in the adhesive composition is relative to 100 parts by mass of copolymer (A), preferably 10 to 1000 parts by mass, more preferably 20 to 500 parts by mass, and even more preferably 50 to 200 parts by mass.

[0151] 1.7 Other Additives (F) The adhesive composition may include, as needed and without impairing the effects of the present invention, other known additives such as crosslinking accelerators, anti-aging agents, fillers, colorants (pigments, dyes, etc.), ultraviolet absorbers, antioxidants, photopolymerization initiators, plasticizers, softeners, surfactants, antistatic agents, and dispersants.

[0152] As the antioxidant, conventionally known antioxidants can be used, such as phenolic antioxidants, sulfur-based antioxidants, and phosphorus-based antioxidants. Phenolic antioxidants are preferred, and hindered phenolic antioxidants are more preferred. The amount of antioxidant relative to 100 parts by mass of copolymer (A) is, for example, 0 to 10 parts by mass, preferably 0.01 to 5 parts by mass, and more preferably 0.1 to 2 parts by mass.

[0153] As the photopolymerization initiator, conventionally known photopolymerization initiators can be used. By using a photopolymerization initiator, an adhesive layer can be formed by photocuring, easily ensuring adhesion and durability. Examples of photopolymerization initiators include acetophenone, 3-methylacetophenone, benzoyladium dimethyl ketal, 2,2-dimethoxy-1,2-diphenylethane-1-one, 1-(4-isopropylphenyl)-2-hydroxy-2-methylpropane-1-one, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinylpropane-1-one, 2-hydroxy-2-methyl-1-phenylpropane-1-one, 1-hydroxycyclohexylphenyl ketone, and other phenylalkyl ketones; benzophenone, 4-chlorobenzophenone, 4,4'-diaminobenzophenone, and other benzophenones; benzoin ethers such as benzoin propyl ether and benzoin ethyl ether; thioxanthones such as 4-isopropylthioxanthone; xanthone; fluorenone; camphorquinone; benzaldehyde; anthraquinone; etc., with phenylalkyl ketones being preferred. These photopolymerization initiators can be used alone or in combination of two or more.

[0154] The amount of photopolymerization initiator relative to 100 parts by mass of copolymer (A) is, for example, 0 to 10 parts by mass, preferably 0.01 to 5 parts by mass, and more preferably 0.1 to 2 parts by mass.

[0155] As the dispersant, conventionally known dispersants can be used. The acid value of the dispersant is preferably 150 mg KOH / g or less, but the lower limit is not particularly limited; it can be 5 mg KOH / g or more, 6 mg KOH / g or more, or 7 mg KOH / g or more. The dispersant preferably has a polyoxyalkylene glycol group. Examples of dispersants include Disperbyk-102, Disperbyk-111, Disperbyk-190, Disperbyk-191, Disperbyk-194N, Disperbyk-2010, Disperbyk-2012, and Disperbyk-2015 manufactured by BYK Chemie Japan Co., Ltd.; TEGO Dispers-715W, TEGO Dispers-750W, and TEGO Dispers-755W manufactured by Evonik Japan Co., Ltd.; and Efka6230 manufactured by BASF.

[0156] The content of the dispersant is not particularly limited, but is, for example, 0 to 30 parts by mass relative to 100 parts by mass of inorganic particles (B), preferably 1 to 15 parts by mass, and more preferably 3 to 10 parts by mass.

[0157] 2. Adhesive layer / laminate An adhesive (adhesive layer) can be formed from the adhesive composition. The method for forming the adhesive layer is not particularly limited, and examples include methods that include applying the adhesive composition to a substrate, and drying and / or photocuring the coating layer obtained in the application process. Particularly preferred are methods that include applying the adhesive composition to a suitable substrate and drying the coating layer obtained in the application process (hereinafter referred to as Method A); and methods that include applying the adhesive composition to a suitable substrate, drying the coating layer obtained in the application process as needed (preferably a solvent evaporation process), and photocuring (hereinafter referred to as Method B). When the adhesive composition contains a photopolymerization initiator, Method B is preferred.

[0158] The drying process is preferably heat drying. The drying temperature can be adjusted appropriately according to the solvent and other components used, for example, 60–160°C, preferably 70–150°C. Furthermore, the drying time can be adjusted appropriately according to the drying temperature.

[0159] In particular, drying in method A is preferably heat drying. The drying temperature can be adjusted appropriately according to the solvent and other components used, for example, 80-160°C, preferably 110-150°C. In addition, the drying time can be adjusted appropriately according to the drying temperature.

[0160] In method B, the preferred drying method is heating. The drying temperature can be adjusted appropriately based on the solvent and other components used, for example, from 60 to 150°C, preferably from 70 to 110°C. Furthermore, the drying time can be adjusted appropriately based on the drying temperature.

[0161] As a method of photocuring (preferably photocuring in method B), methods of irradiating with active energy rays can be listed. A particularly preferred method is to irradiate the precursor layer, obtained by coating an adhesive composition onto a substrate and drying it before curing, preferably under a nitrogen atmosphere and / or while the precursor layer is laminated with a release film (preferably with both sides of the precursor layer laminated with a release film). Examples of such active energy rays include ultraviolet light, laser rays, alpha rays, beta rays, gamma rays, X-rays, and electron beams. From the viewpoints of good controllability, operability, and cost, ultraviolet light is preferred. Ultraviolet light with a wavelength of 200 nm or more and 400 nm or less is more preferred. Ultraviolet light can be irradiated using light sources such as high-pressure mercury lamps, microwave excitation lamps, chemical lamps, black lights, LEDs, and metal halide lamps.

[0162] The substrate is not particularly limited and can be a release film or a component for which adhesion is desired (e.g., an optical film or other optical component). By using an optical component (e.g., an optical film) as the substrate, optical components (e.g., optical films) with laminated adhesive (adhesive layers) can be manufactured. Furthermore, by using a release film as the substrate, adhesive (adhesive layers) can be transferred onto various components. As a result, components with laminated adhesive (adhesive layers) (e.g., optical films or other optical components) can be manufactured.

[0163] As a release film, conventionally known release films can be used, and plastic films are preferred in terms of cost and excellent surface smoothness.

[0164] This method enables the manufacture of a laminate comprising a substrate and an adhesive layer laminated on the substrate. Such a laminate is also included within the scope of this invention.

[0165] As a laminate containing an adhesive layer formed by the adhesive composition of the present invention, the adhesive layer can be laminated on any substrate (e.g., the release film or optical component described above), and preferably on an optical component such as an optical film.

[0166] It should be noted that, as long as the substrate and the adhesive layer are directly laminated, other components can be laminated on the surface of the substrate where the adhesive layer is not laminated and on the surface of the substrate where the adhesive layer is not laminated.

[0167] Furthermore, the adhesive layer thus formed comprises a copolymer (A) and inorganic particles (B). Preferably, the copolymer (A) in this adhesive layer is... A copolymer (A) comprising aromatic structural units (A1) and hydroxyl-containing structural units (A2), and The content of the structural unit (A2) is 1 to 40% by mass of the copolymer (A) (preferably the sum of structural units (A1) and (A2)) in 100% by mass of the copolymer (A), which is the same as that of the copolymer (A) in the adhesive composition. In particular, the adhesive layer obtained by method A has the same properties as the adhesive composition, except for the properties that change due to drying, such as the amount of monomer (a) and solvent (e.g., composition, type, amount of each component).

[0168] Hereinafter, the adhesive layer comprising a copolymer (A) and inorganic particles (B), wherein the copolymer (A) comprises structural units (A1) and structural units (A2), and the content of the structural units (A2) is 1 to 40% by mass in 100% by mass of the copolymer (A) is referred to as the adhesive layer of the present invention.

[0169] The copolymer (A) included in the adhesive layer of the present invention comprises structural units (A1) and (A2), and may include structural units (A3) as needed (specifically, structural units (A31) to (A42)). Specific examples and preferred examples of these structural units are the same as those described above for copolymer (A). The content of each structural unit in 100% by mass of copolymer (A) in the adhesive layer of the present invention is shown below for example.

[0170] The content of structural unit (A1) is, for example, 40 to 99% by mass, preferably 50 to 95% by mass, and more preferably 70 to 90% by mass.

[0171] The content of structural unit (A2) is, for example, 1 to 40% by mass, preferably 3 to 30% by mass, and more preferably 7 to 25% by mass.

[0172] The content of the structural unit (A3) is, for example, 0 to 50% by mass, preferably 1 to 50% by mass, more preferably 1 to 40% by mass, even more preferably 5 to 25% by mass, and particularly preferably 5 to 20% by mass.

[0173] The content of the structural unit (A31) is, for example, 0 to 50% by mass, preferably 5 to 40% by mass, more preferably 10 to 30% by mass, and even more preferably 10 to 20% by mass.

[0174] The content of the structural unit (A32) is, for example, 0 to 50% by mass, preferably 1 to 30% by mass, more preferably 5 to 20% by mass, and even more preferably 5 to 10% by mass.

[0175] The content of the structural unit (A33) is, for example, 0 to 50% by mass, preferably 5 to 40% by mass, and more preferably 10 to 30% by mass.

[0176] The content of the structural unit (A34) is, for example, 0 to 50% by mass, preferably 0 to 30% by mass, and more preferably 1 to 20% by mass.

[0177] The content of the structural unit (A35) is, for example, 0 to 50% by mass, preferably 0 to 10% by mass, and more preferably 0 to 5% by mass.

[0178] The content of the structural unit (A36) is, for example, 0 to 50% by mass, preferably 0 to 30% by mass, more preferably 0 to 10% by mass or 0% by mass.

[0179] The content of the structural unit (A37) is, for example, 0 to 50% by mass, preferably 0 to 20% by mass, and more preferably 0 to 10% by mass.

[0180] The content of the structural unit (A38) is, for example, 0 to 50% by mass, preferably 0 to 20% by mass, and more preferably 0 to 10% by mass.

[0181] The content of the structural unit (A39) is, for example, 0 to 50% by mass, preferably 0 to 20% by mass, and more preferably 0 to 10% by mass.

[0182] The content of the structural unit (A40) is, for example, 0 to 50% by mass, preferably 0 to 20% by mass, and more preferably 0 to 10% by mass.

[0183] The content of the structural unit (A41) is, for example, 0 to 50% by mass, preferably 0 to 20% by mass, and more preferably 0 to 10% by mass.

[0184] The content of the structural unit (A42) is, for example, 0 to 50% by mass, preferably 0 to 20% by mass, and more preferably 0 to 10% by mass.

[0185] The total content of structural unit (A1) and structural unit (A2) in 100% by mass of copolymer (A) in the adhesive layer is, for example, 50-100% by mass, preferably 60-99% by mass, more preferably 75-95% by mass, and may also be 85-100% by mass or 95-100% by mass. Furthermore, the mass ratio (A1 / A2) of structural unit (A1) to structural unit (A2) is, for example, 50 / 50-99 / 1, preferably 70 / 30-98 / 2, more preferably 75 / 25-95 / 5, even more preferably 80 / 20-90 / 10, and particularly preferably 83 / 17-88 / 12.

[0186] The weight-average molecular weight of the copolymer (A) in the adhesive layer of the present invention is, for example, 500,000 to 3,000,000, preferably 700,000 to 2,500,000, more preferably 1,000,000 to 2,000,000, and particularly preferably 1,200,000 to 1,500,000.

[0187] On the other hand, due to drying and light curing, the content of monomers (a) such as aromatic monomers (a1), hydroxyl-containing monomers (a2), and other monomers (a3) ​​in the adhesive layer is generally less than that in the adhesive composition. However, the dispersibility of inorganic particles (B) is maintained even with a reduction in monomers (a), and the adhesive layer maintains high transparency even with an increase in thickness. It should be noted that the amount of monomers (a) in the adhesive layer of the present invention is, for example, less than 1 part by weight relative to 100 parts by weight of copolymer (A), preferably less than 0.5 parts by weight, and more preferably less than 0.1 parts by weight.

[0188] The amount of inorganic particles (B) in the adhesive layer of the present invention is, for example, 20 to 2000 parts by mass relative to 100 parts by mass of the copolymer (A), preferably 50 to 1500 parts by mass, more preferably 80 to 1000 parts by mass, and even more preferably 80 to 850 parts by mass, or may be 80 to 700 parts by mass or 80 to 350 parts by mass. By adjusting the proportion of inorganic particles (B) within the above range, it is easier to balance refractive index and transparency.

[0189] The total content of copolymer (A) and inorganic particles (B) in the adhesive layer of the present invention is preferably 80 to 100% by mass in 100% by mass of the adhesive layer, more preferably 90 to 99.9% by mass, and even more preferably 95 to 99.9% by mass.

[0190] When the thickness of the adhesive layer of the present invention is set to 100µm, the haze is, for example, 1.0% or less, preferably 0.8% or less, more preferably 0.5% or less, and even more preferably 0.3% or less.

[0191] The thickness of the adhesive layer of the present invention is not particularly limited, and can be, for example, 1–2000 µm, 30–1000 µm, 50–700 µm, or about 100–500 µm. In particular, the adhesive layer of the present invention is formed from a specific adhesive composition, so even when it is a thick film (e.g., 50 µm or more, preferably 100 µm or more), transparency and refractive index can be balanced, making it suitable for bonding optical films. Furthermore, the thickness of the adhesive layer can be 2–300 µm, 3–200 µm, or 5–100 µm.

[0192] It should be noted that the haze of the adhesive layer of the present invention, regardless of its thickness, is, for example, less than 1.0%, preferably less than 0.8%, more preferably less than 0.5%, and even more preferably less than 0.3%, with a lower limit of about 0.1%.

[0193] Furthermore, the copolymer (A) constituting the adhesive layer of the present invention contains hydroxyl-containing structural units (A2), so even when placed under humidified conditions, the increase in haze is small. The haze after the humidification test (temperature 60°C, relative humidity 95%RH, 500 hours) described later is, for example, 13% or less, preferably 10% or less, more preferably 7% or less, even more preferably 4% or less, and the lower limit may also be about 1%.

[0194] The refractive index of the adhesive layer of the present invention is, for example, 1.58 to 1.80, preferably 1.60 to 1.75, and more preferably 1.61 to 1.72. When the refractive index of the adhesive layer is within the range described above, it is suitable for bonding optical films.

[0195] The adhesive composition and adhesive layer can be used for a variety of applications, and are preferably used for bonding optical components such as optical films, that is, preferably for use as an adhesive layer laminated on optical components such as optical films. Specifically, it is preferably used for bonding optical components such as optical films in image display devices such as liquid crystal displays, organic EL displays, plasma displays (PDPs), micro LED displays, curved displays, and flexible displays. In particular, the adhesive composition and adhesive layer are preferably used for thin adhesive optical films used in large liquid crystal panels.

[0196] Examples of optical films include polarizing plates, phase retardation plates used to prevent color distortion, optical compensation films such as viewing angle expansion films used to improve the viewing angle of liquid crystal displays, brightness enhancement films used to improve the contrast of displays, light extraction films used to improve the light extraction efficiency of surface emitters, and other components formed by stacking these layers.

[0197] This application claims priority based on Japanese Patent Application No. 2024-053700, filed March 28, 2024; Japanese Patent Application No. 2024-082135, filed May 20, 2024; and Japanese Patent Application No. 2024-179874, filed October 15, 2024. The entire contents of the descriptions of Japanese Patent Application No. 2024-053700, No. 2024-082135, and No. 2024-179874 are incorporated herein by reference.

[0198] Example The present invention is illustrated below with specific examples, but it is not limited to these examples. Modifications can be made to implement the invention within the scope of the foregoing / hereafter described, and all such modifications are included within the technical scope of the present invention. It should be noted that in the following description, "parts" refers to "parts by mass". Furthermore, unless otherwise specified, the determination of operation and physical properties is performed at room temperature (23°C) and relative humidity (55%RH).

[0199] 1. Measurement Method 1.1 Weight-average molecular weight (Mw) The weight-average molecular weight (Mw) of the (meth)acrylate copolymer (A) was determined by GPC (gel permeation chromatography) under the following conditions: Analytical device: HLC-8120GPC manufactured by Tosoh Corporation.

[0200] Chromatographic column: Made by Tosoh Corporation, G7000HXL+GMHXL+GMHXL.

[0201] Column dimensions: 7.8mm each φ×30cm, total 90cm.

[0202] Column temperature: 40℃.

[0203] Flow rate: 0.8 ml / min.

[0204] Injection volume: 100µl.

[0205] Eluent: Tetrahydrofuran.

[0206] Detector: Differential refractometer (RI).

[0207] Standard sample: polystyrene.

[0208] 1.2 Amount of (meth)acrylate monomers (a) The residual amount and composition of (meth)acrylate monomers (a) were determined using GC / MS (GC-Agilent GC7980A, MS-Nippon Electronics Q-1050GC).

[0209] 1.3 Compositional Identification of Copolymer (A) The composition of the copolymer was determined by NMR. The NMR peaks of the copolymer components were assigned using references to the "Aldrich Library of NMR Spectra" and the "13C NMR Spectra" from Sadtler Research Lab. Furthermore, the copolymer composition was determined using... 1 H and 13 The integral value of C was calculated. It should be noted that the measuring apparatus used was a JNM-GX400 (manufactured by Nippon Electronics Co., Ltd.), the solvent used was deuterated chloroform, and the measuring temperature was 27°C.

[0210] 1.4 refractive index The refractive index of the adhesive layer (thickness: 20 µm) obtained in the examples or comparative examples was determined using an Abbe refractometer at 25 °C as a value relative to the sodium D line.

[0211] 1.5 haze In the examples or comparative examples, after forming an adhesive layer (thickness: 100µm) on the release-treated surface of the PET film, another PET film with a release-treated surface is bonded to the exposed adhesive layer to create an adhesive sheet.

[0212] Peel off the release film from one side of the obtained adhesive sheet, and roll-press the exposed adhesive surface onto alkali-free glass (82mm × 53mm × 0.5mm thickness). Next, peel off the release film from the other side and roll-fit it onto alkali-free glass (82mm × 53mm × 0.5mm thickness). Then, perform autoclaving (50°C, gauge pressure 0.4MPa, 20 minutes) for final bonding to prepare evaluation samples.

[0213] The haze of the obtained evaluation samples was measured using a haze meter (NDH5000, manufactured by Nippon Denshoku Kogyo Co., Ltd.) according to JIS K7136 (2000) at an environment of 25°C and 55%RH.

[0214] 1.6 Durability (Heating Test, Humidification Test, HS Test) An organic EL display device with an optical compensation layer and a polarizing plate having an adhesive layer (thickness: 20µm) prepared in the embodiments or comparative examples was manufactured in the manner described below, and a sample for durability evaluation was prepared. The obtained sample was subjected to the following tests, its appearance was visually observed, and it was evaluated according to the following criteria.

[0215] (1) Treated at 85°C for 500 hours (heating test).

[0216] (2) Treated for 500 hours at a temperature of 60℃ and a relative humidity of 95%RH (humidification test).

[0217] (3) After being placed at 85°C for 30 minutes, it is placed at -40°C for 30 minutes as one cycle. 300 cycles (300 hours) of treatment are carried out with 1 cycle of 1 hour. (Thermal shock (HS) test).

[0218] -Evaluation Criteria- ◎: The end is completely free of air bubbles.

[0219] ○: There are a few air bubbles at the end, but it is not a problem in practical use.

[0220] Δ: There are air bubbles at the end, but this is not a problem in practice unless for special purposes.

[0221] ×: There are a significant number of air bubbles at the end, which poses a practical problem.

[0222] 1.7 Haze (%) after humidification test The samples used for the above-mentioned durability humidification test were taken out and left to stand at room temperature (23°C, 55%RH) for 3 hours. Then, the haze was measured using a haze meter (Nippon Denshoku Kogyo Co., Ltd., NDH5000) according to JIS K7136 (2000) at a temperature of 25°C and a relative humidity of 55%RH.

[0223] 1.8 Coating properties Immediately after forming the adhesive layer (thickness: 20µm) of the examples or comparative examples, visually inspect the surface condition of the adhesive layer and evaluate it according to the following criteria. In the 5-stage evaluation, 5 is the best, and 3 or above is practical.

[0224] 5: No coating streaks, no uneven coating.

[0225] 4: Some parts may have slight coating streaks or slight uneven coating.

[0226] 3: Slight coating streaks or slight uneven coating are present throughout.

[0227] 2: Severe coating streaks or severe uneven coating exist in parts or all of the product.

[0228] 1: Unable to form a uniform coating surface.

[0229] 2. Preparation of (meth)acrylate copolymer (A) [Manufacturing Examples 1-16] In a four-necked flask equipped with a stirring blade, thermometer, nitrogen inlet pipe, and cooler, aromatic monomers (a1), hydroxyl-containing monomers (a2), other monomers (a3), and polymerization initiator were added according to the mass parts shown in Table 1. Additionally, 100 parts by mass of ethyl acetate were added. Nitrogen gas was introduced while the mixture was slowly stirred. After nitrogen purging, the liquid temperature in the flask was controlled at approximately 60°C, and the polymerization reaction was carried out for 2 hours to prepare solutions of (meth)acrylate copolymers (A-1) to (A-16). The characteristics of the copolymers (A) and residual monomers (a) in the solutions are shown in Table 1.

[0230] [Manufacturing Examples 17-20] The aromatic monomers (a1), hydroxyl-containing monomers (a2), other monomers (a3), and polymerization initiators added to the four-necked flask are shown in Table 2. The polymerization conditions are also shown in Table 2. Except as in Manufacturing Examples 1-16, solutions of (meth)acrylate copolymers (A-17) to (A-20) were prepared. The characteristics of the copolymers (A) and residual monomers (a) in the solutions are shown in Table 2. It should be noted that the polymerization temperature of the reflux polymerization was 86°C → 79°C. Specifically, in the early stages of polymerization, the monomers were also refluxed with the solvent, so the reflux temperature was high at 86°C. However, as the polymerization reaction proceeded, the monomer ratio continued to decrease, and eventually, due to the presence of residual monomers, the temperature decreased to around 79°C, which is slightly higher than that of ethyl acetate used as the solvent.

[0231] [Manufacturing Examples 21-28] The aromatic monomers (a1), hydroxyl-containing monomers (a2), other monomers (a3), and polymerization initiators added to the four-necked flask are shown in Table 2. The reaction temperature and time (polymerization conditions) are also shown in Table 2. Except as in Manufacturing Examples 1-16, solutions of (meth)acrylate copolymers (A-21) to (A-28) were prepared. The characteristics of the copolymers (A) and residual monomers (a) in the solutions are shown in Table 2.

[0232]

[0233]

[0234] The symbols in Tables 1 and 2 have the following meanings.

[0235] A-BPML: p-Phenylenyl acrylate (manufactured by Shin-Nakamura Chemical Industry Co., Ltd.)

[0236] NMT-A: Naphthylmethyl acrylate (manufactured by Kyoeisha Chemical Co., Ltd.).

[0237] A-LEN-10: Ethoxylated o-phenylphenol acrylate (A-LEN-10, manufactured by Shin-Nakamura Chemical Industry Co., Ltd.).

[0238] POB-A: Light Acrylate POB-A (manufactured by Kyoei Chemical Co., Ltd.).

[0239] PhEA: Phenoxyethyl acrylate (manufactured by Kyoeisha Chemical Co., Ltd.)

[0240] BzA: Benzyl acrylate (manufactured by Osaka Organic Chemical Industry Co., Ltd.).

[0241] 4HBA: 4-hydroxybutyl acrylate (manufactured by Osaka Organic Chemical Industry Co., Ltd.).

[0242] HEAA: N-hydroxyethylacrylamide (manufactured by KJ Chemicals Co., Ltd.).

[0243] IBXA: Isoborneol acrylate (Nippon Shokubai Co., Ltd.)

[0244] ACMO (registered trademark): N-acryloylmorpholine (manufactured by KJ Chemicals Co., Ltd.)

[0245] BA: n-butyl acrylate (manufactured by Nippon Shokubai Co., Ltd.).

[0246] 2EHA: 2-Ethylhexyl acrylate (Nippon Shokubai Co., Ltd.)

[0247] MEA: Ethyl methoxyacrylate (Nippon Shokubai Co., Ltd.)

[0248] AA: Acrylic acid (Nippon Shokubai Co., Ltd.).

[0249] AIBN: 2,2'-Azobisisobutyronitrile (manufactured by Fujifilm and Waku Pure Chemical Industries, Ltd.)

[0250] 3. Adhesive composition, adhesive layer Examples 1-25, Comparative Examples 1-8 An adhesive composition was prepared by mixing a solution of (meth)acrylate copolymer (A) obtained in Examples 1 to 28 (the amount of (meth)acrylate copolymer (A) in the solution is 100 parts by mass) with inorganic particles (B) (converted amount of solid components) shown in Tables 3 to 4, silane coupling agent (C), crosslinking agent (D), and antioxidant (converted amount of active ingredients).

[0251] The obtained adhesive composition was coated onto one side of a 38µm thick polyethylene terephthalate (PET) film (Mitsubishi Chemical Corporation, MRF38, without oligomer barrier layer) that had undergone a release treatment (silicone treatment), and the thickness of the dried adhesive layer reached the specified coating thickness (target adhesive layer thickness). Then, it was heat-treated at 120°C for 2 minutes to form the adhesive layer. It should be noted that the heat treatment was performed using a floating drying method with hot air directly supplied from above and below the film.

[0252] Examples 26-35 A solution of the (meth)acrylate copolymer (A) obtained in Examples 6 and 17-20 (the amount of (meth)acrylate copolymer (A) in the solution is 100 parts by mass) was mixed with the inorganic particles (B) (converted amount of solid components) shown in Table 4, the crosslinking agent (D), and the photopolymerization initiator to prepare an adhesive composition.

[0253] The obtained adhesive composition was coated onto one side of a 38µm thick polyethylene terephthalate (PET) film (Mitsubishi Chemical Corporation, MRF38, without oligomer barrier layer) that had undergone a release treatment (silicone treatment), and the thickness of the dried adhesive layer reached the specified coating thickness (target adhesive layer thickness). Subsequently, in Examples 26-28 and 32-35, the film was heated at 80°C for 1 minute, and in Examples 29-31, it was heated at 100°C for 1 minute to evaporate the solvent. Afterwards, the oxygen concentration was set to below 0.1% under nitrogen purging conditions, and the film was heated under a metal halide lamp at an illuminance of 350mW / cm². 2 Cumulative light intensity 1000 mJ / cm 2The film is then cured to form an adhesive layer. It should be noted that the heat treatment is performed using a floating drying method, where hot air is directly supplied from above and below the film.

[0254] The properties of the obtained adhesive layer were evaluated. The results are shown in Tables 3 and 4.

[0255]

[0256]

[0257] The symbols in Tables 3 and 4 have the following meanings.

[0258] [ZP-158]: Zirconia microparticle dispersion (manufactured by Nippon Shokubai Co., Ltd., with a volume average particle size of 11 nm, a particle refractive index of 1.8, and a dispersion of methyl ethyl ketone, with a solid content concentration of 70% by mass).

[0259] [LP-4]: Zirconia microparticle dispersion (a dispersion obtained according to the [Preparation of Zirconia Microparticles (LP-4)] below, with a volume average particle size of 18 nm, a particle refractive index of 1.86, and a propylene glycol monomethyl ether dispersion with a solid content concentration of 70% by mass).

[0260] [KBM-403]: 3-glycidoxypropyltrimethoxysilane (manufactured by Shin-Etsu Chemical Co., Ltd.)

[0261] [D-110N]: Takenate (registered trademark) D-110N (manufactured by Mitsui Chemicals Co., Ltd.); 75% ethyl acetate solution of the adduct of phenyl dimethyl diisocyanate (XDI) and trimethylolpropane; 3 isocyanate groups per molecule; number average molecular weight Mn=700.

[0262] [A-DPH]: NK Ester A-DPH (manufactured by Shin-Nakamura Chemical Industry Co., Ltd.); dipentaerythritol polyacrylate; penta- to hexafunctional monomer.

[0263] [W-400]: ANTAGE W-400 (manufactured by Kawaguchi Chemical Industry Co., Ltd.).

[0264] [Omnirad 184]: 1-Hydroxycyclohexylphenyl ketone (manufactured by IGM Resins BV).

[0265] [Manufacturing of Zirconia Particles (LP-4)] A solution of 2-ethylhexanoate zirconium mineral oil (782 parts, zirconium content 44% by mass) was mixed with pure water (268 parts). The resulting mixture was placed in an autoclave equipped with a stirrer, and the atmosphere inside the autoclave was purged with nitrogen. The mixture was then heated to 210°C and maintained at this temperature for 16 hours to produce zirconium oxide (zirconia) particles. The reaction mixture was then removed, the precipitate accumulated at the bottom was filtered off, washed with acetone, and dried. The dried precipitate (100 parts) was dispersed in toluene (700 parts) to obtain a cloudy white solution. As a purification step, the solution was filtered again using quantitative filter paper (Advantech Toyo Co., Ltd., No. 5C) to remove coarse particles from the precipitate. Toluene was further removed by vacuum concentration of the filtrate, and the white zirconium oxide particles were recovered.

[0266] It should be noted that the number-average particle size of the recovered zirconia particles was determined using an ultra-high resolution field emission scanning electron microscope (Hitachi High Technology Co., Ltd., S-4800). Zirconia particles were observed at 150,000x magnification, and the length of the long axis of any 100 particles was measured. The average value of these measurements was taken as the number-average particle size. The number-average particle size of the zirconia particles determined by electron microscopy was 18 nm.

[0267] The zirconia microparticles obtained above, propylene glycol monomethyl ether, and DISPER BYK-111 (manufactured by BYK Chemie Japan Co., Ltd.) were mixed and stirred at a mass ratio of zirconia microparticles / propylene glycol monomethyl ether / BYK-111 = 65.0 / 30.0 / 5.0 to prepare a zirconia microparticle dispersion (LP-4). It should be noted that the volume average particle size of the zirconia microparticles in the obtained dispersion is 18 nm, and the particle refractive index is 1.86.

[0268] It should be noted that the organic EL display devices manufactured in the following manner were used in the durability evaluation and haze evaluation after the humidification test.

[0269] 4. Organic EL display devices 4.1 Fabrication of Polarizing Plates Prepare an A-PET (amorphous polyethylene terephthalate) film (manufactured by Mitsubishi Chemical Corporation, trade name: Novaclear (registered trademark) SH046, thickness 200µm) as the substrate, and perform corona treatment on the surface (corona discharge amount 58W). min / m 2Additionally, a polyvinyl alcohol (PVA) with 1% by mass of acetylacetyl-modified polyvinyl alcohol (manufactured by Mitsubishi Chemical Corporation, trade name: Gohsefimer (trademark) Z200, degree of polymerization 1200, degree of saponification ≥99.0%, degree of acetylacetyl modification 4.6%) was prepared. This PVA was coated onto the corona-treated surface of an A-PET film to a dry film thickness of 12µm, and dried with hot air at 60°C for 10 minutes. Thus, a laminate with a polyvinyl alcohol (PVA) resin layer on a substrate was formed.

[0270] Next, the laminate was first stretched to 2.0 times its original size in air at 130°C to obtain a stretched laminate. Then, the stretched laminate was immersed in a boric acid-insoluble aqueous solution at 30°C for 30 seconds to insolublee the PVA-based resin layer containing oriented polyvinyl alcohol molecules. The boric acid content in this boric acid-insoluble aqueous solution was set to 3% by mass relative to 100% by mass of water. The stretched laminate was then dyed to generate a colored laminate. The colored laminate was obtained by immersing the stretched laminate in a dyeing solution containing iodine and potassium iodide at 30°C, causing the PVA-based resin layer in the stretched laminate to adsorb iodine. The iodine concentration and immersion time were adjusted so that the monomer transmittance of the resulting polarizer was 44.5%. Specifically, the dyeing solution used water as a solvent, with an iodine concentration in the range of 0.08% by mass to 0.25% by mass, and a potassium iodide concentration in the range of 0.56% by mass to 1.75% by mass. The concentration ratio of iodine to potassium iodide is 1:7.

[0271] Next, a cross-linking process is performed on the PVA molecules of the iodine-adsorbed PVA-based resin layer by immersing the colored laminate in a boric acid cross-linking aqueous solution at 30°C for 60 seconds. In this process, the boric acid content in the boric acid cross-linking aqueous solution is set to 3% by mass relative to 100% of water, and the potassium iodide content is set to 3% by mass relative to 100% of water. Further, the obtained colored laminate is stretched in the boric acid aqueous solution at a stretching temperature of 70°C in the same direction as the stretching in air to a ratio of 2.7 times, resulting in a final stretch ratio of 5.4 times, to obtain a substrate / polarizer laminate. The polarizer thickness is 5µm. In this process, the boric acid content in the boric acid cross-linking aqueous solution is set to 6.5% by mass relative to 100% of water, and the potassium iodide content is set to 5% by mass relative to 100% of water. The obtained laminate is removed from the boric acid aqueous solution, and the boric acid adhering to the polarizer surface is cleaned with an aqueous solution containing 2% by mass of potassium iodide relative to 100% of water. The cleaned laminate is then dried with hot air at 60°C.

[0272] On the surface of the polarizer in the aforementioned substrate / polarizer laminate, an acrylic film with a thickness of 40 µm is bonded using a PVA-based adhesive. Further, a polarizer plate with a protective layer / polarizer / resin substrate structure is obtained.

[0273] 4.2 Fabrication of the liquid crystal alignment and curing layer constituting the first optical compensation layer Following the order described in paragraphs

[0151] to

[0156] of Japanese Patent Application Publication No. 2006-133652, a liquid crystal alignment curing layer (first optical compensation layer) is formed on a substrate (TAC film). It should be noted that the direction of the rubbing treatment is set to be 15° counterclockwise from the absorption axis direction of the polarizer when viewed from the visual identification side, when bonded to the polarizer. The thickness of the first optical compensation layer is 1.7 µm, and the in-plane phase difference Re(550) is 270 nm. Furthermore, the first optical compensation layer is a negative A-plate exhibiting refractive index characteristics of nx = nz > ny. In addition, no protrusions with a height greater than 0.4 µm are observed on the surface of the first optical compensation layer (negative A-plate).

[0274] 4.3 Fabrication of the liquid crystal alignment and curing layer constituting the second optical compensation layer A liquid crystal composition (coating solution) was prepared by dissolving 10g of a polymerizable liquid crystal compound (manufactured by BASF, trade name "PalioColor (registered trademark) LC242") that displays a nematic liquid crystal phase and 3g of a photopolymerization initiator for the polymerizable liquid crystal compound (Omnirad (registered trademark) 907; manufactured by IGM Resins BV) in 40g of toluene.

[0275] A photoalignment film was coated onto the surface of a polyethylene terephthalate (PET) film (38 µm thick), and a photoalignment treatment was performed. The direction of the photoalignment treatment was set to be 75° counterclockwise from the absorption axis of the polarizer when viewed from the visual identification side, as when the film is bonded to the polarizer. The aforementioned liquid crystal composition was then coated onto the photoaligned surface using a bar coater and dried at 90°C for 2 minutes, thereby aligning the liquid crystal compound. The liquid crystal layer thus formed was irradiated with a metal halide lamp at 1 mJ / cm². 2 The light is used to cure the liquid crystal layer, thereby forming a liquid crystal alignment and curing layer (second optical compensation layer) on the substrate (PET film). The thickness of the second optical compensation layer is 1.2µm, and the in-plane phase difference Re(550) is 140nm. Furthermore, the second optical compensation layer is a positive A plate exhibiting the refractive index characteristics of nx>ny=nz.

[0276] 4.4 Fabrication of a polarizing plate with an optical compensation layer The A-PET film of the substrate is peeled off from the polarizer obtained above, and the first optical compensation layer in the substrate / first optical compensation layer laminate is transferred to the peeling surface using a UV-curable adhesive. Further, the second optical compensation layer in the substrate / second optical compensation layer laminate is transferred to the surface of the first optical compensation layer using a UV-curable adhesive. Thus, a polarizer with an optical compensation layer is obtained, having a structure of protective layer / polarizer / first optical compensation layer (negative A-plate: λ / 2 plate) / second optical compensation layer (positive A-plate: λ / 4 plate).

[0277] 4.5 Fabrication of a polarizing plate with adhesive layer and optical compensation layer On the polarizer side (opposite to the protective film side) where the adhesive layer is to be formed on the polarizer with the optical compensation layer obtained above, a corona discharge of 80W is applied. min / m 2 A corona treatment is performed to form an easy-to-adhere layer. Then, the PET film with the adhesive layer is laminated in such a way that the formed easy-to-adhere layer is in contact with the adhesive layer (thickness: 20µm) obtained in the example or comparative example to produce a polarizing plate with an adhesive layer and an optical compensation layer.

[0278] 4.6 Fabrication of Organic EL Display Devices The obtained polarizing plate with adhesive and optical compensation layers was cut into 100mm × 50mm dimensions. A Samsung Electronics Corporation-manufactured smartphone (Galaxy-S23) was disassembled, and the organic EL display device was removed. The polarizing film attached to the organic EL display device was peeled off, and in its place, the cut polarizing plate with optical compensation layer was attached to obtain the organic EL display device.

[0279] Industrial availability The adhesive composition and adhesive layer of the present invention can be used in various components, and are preferably used for bonding and adhesion of optical films.

Claims

1. An adhesive composition for optical films, comprising a (meth)acrylate copolymer (A), a (meth)acrylate monomer (a), and inorganic particles (B), The copolymer (A) comprises structural units (A1) derived from aromatic hydrocarbon-containing (meth)acrylate monomers (a1) and structural units (A2) derived from hydroxyl-containing (meth)acrylate monomers (a2). The monomer (a) comprises an aromatic hydrocarbon group-containing (meth)acrylate monomer (a1) and a hydroxyl group-containing (meth)acrylate monomer (a2). The content of the structural unit (A2) is 1-40% by mass in 100% by mass of the copolymer (A). The content of the monomer (a) is 7 to 30% by mass in 100% by mass of the copolymer (A) and the monomer (a).

2. The adhesive composition according to claim 1, wherein, The monomer (a1) is at least one selected from the group consisting of aryl esters of (meth)acrylic acid, aralkyl esters of (meth)acrylic acid, and aryloxyalkyl esters of (meth)acrylic acid. The aryl esters, aralkyl esters, and aryloxyalkyl esters of (meth)acrylic acid are optionally bonded with aryl, arylalkyl, aryloxy, or aryloxyalkyl groups. The aryl esters, aralkyl esters, and aryloxyalkyl esters of (meth)acrylic acid are optionally epoxide-modified.

3. The adhesive composition according to claim 1, wherein, The copolymer (A) comprises structural units (A3) derived from monomers other than aromatic hydrocarbon (meth)acrylate monomers (a1) and hydroxyl-containing (meth)acrylate monomers (a2). The (meth)acrylate monomer (a) includes other monomers (a3) ​​besides the (meth)acrylate monomer (a1) containing an aromatic hydrocarbon group and the (meth)acrylate monomer (a2) containing a hydroxyl group. The content of the structural unit (A3) is less than 50% by mass in 100% by mass of the copolymer (A).

4. The adhesive composition according to claim 3, wherein, The other monomers (a3) ​​comprise at least one from the group consisting of (meth)acrylate monomers containing alicyclic hydrocarbon groups, (meth)acrylate monomers containing nitrogen atoms, (meth)acrylate monomers containing alkoxyalkyl groups, low Tg (meth)acrylate alkyl monomers with a glass transition temperature of less than -20°C for homopolymers, and monomers containing acid groups.

5. The adhesive composition according to claim 1, wherein, The copolymer (A) has a weight-average molecular weight of 500,000 to 3,000,000.

6. The adhesive composition according to claim 1, wherein, The inorganic particle (B) is a particle composed of at least one selected from the group consisting of alumina, titanium oxide, zirconium oxide, indium oxide, zinc oxide, tin oxide, lanthanum oxide, yttrium oxide, cerium oxide, magnesium oxide, niobium oxide, tantalum oxide, indium tin oxide, antimony tin oxide, barium titanate, strontium titanate, perovskite and spinel.

7. The adhesive composition according to claim 1, wherein, The volume average particle size of the inorganic particles (B) is 1–100 nm.

8. The adhesive composition according to claim 1, wherein, In the particle size determination of the inorganic particles (B) using dynamic light scattering, the ratio of the cumulative 90% particle size D90 of the volume reference to the cumulative 50% particle size D50 of the volume reference (D90 / D50) is 3.0 or less.

9. The adhesive composition according to claim 1, wherein, The refractive index of the adhesive layer formed from the adhesive composition is 1.58 to 1.

80.

10. The adhesive composition according to claim 1, wherein, The haze of an adhesive layer with a thickness of 100µm formed from the adhesive composition is less than 1.0%.

11. An adhesive layer formed from an adhesive composition according to any one of claims 1 to 10.

12. Use of a composition according to any one of claims 1 to 10, for use as an adhesive laminated on an optical film.

13. A laminate comprising an optical film and an adhesive layer according to claim 11 laminated on the optical film.

14. A method for manufacturing an optical film laminated with an adhesive, comprising: The coating process of applying the composition according to any one of claims 1 to 10 onto a substrate; and The process of forming an adhesive layer by drying and / or photocuring the coating layer obtained in the coating process. The substrate used in the coating process is an optical film, or the process may further include a transfer process after the adhesive layer formation process to transfer the adhesive layer onto the optical film.

15. An adhesive layer comprising an (meth)acrylate copolymer (A) and inorganic particles (B) for use in optical films. The thickness of the adhesive layer is 50µm or more. The haze of the adhesive layer is below 1.0%. The copolymer (A) comprises structural units (A1) derived from aromatic hydrocarbon-containing (meth)acrylate monomers (a1) and structural units (A2) derived from hydroxyl-containing (meth)acrylate monomers (a2). The content of the structural unit (A2) is 1 to 40% by mass in 100% by mass of the copolymer (A).

Citation Information

Patent Citations

  • Retardation plate, polarizing plate and liquid crystal display

    JP2006133652A

  • Adhesive composition, adhesive and adhesive sheet

    JP2017128732A

  • Game machine

    JP2024053700A

  • Ball bearing

    JP2024082135A

  • Wheel

    JP2024179874A